Retaining fruiting trees in the agricultural matrix is important for bird-mediated seed dispersal in a fragmented forest landscape - Jelaine Lim Gan; Katrin M. Meyer; Marion Pfeifer; Terence Craig Soroño; Erwin Somera Torio; Merlijn van Weerd; Marites Gatan-Balbas; Mark David Foster Shirley (Ecological Modelling, 2026)

Jaguar Range‐Wide Connectivity: Prioritising Core Areas and Corridors Between and Within Protected Areas and Indigenous Lands - Guilherme Costa Alvarenga; Caroline C. Sartor; Ana Carolina Srbek‐Araujo; Ana Cristina Mendes‐Oliveira; Bart Harmsen; Carlos De Angelo; Carolina Franco Esteves; Claudia Bueno de Campos; Daiana Jeronimo Polli; Diego F. Passos Viana; Diogo Maia Gräbin; Emiliano Donadio; et al. (Global Change Biology, 2026)
Anthropogenic habitat transformation has led to population declines and increasing isolation of populations of many species, particularly top predators, where small and fragmented populations often experience limited dispersal and reduced genetic diversity. Jaguars ( Panthera onca ), for example, have lost half of their historical range and most populations outside the Amazon biome are small, isolated and highly threatened. Here, we assess jaguar population connectivity across the species' range by identifying and ranking core areas and dispersal corridors, including linkages among Protected Areas and Indigenous Lands (hereafter, PAs). We used cumulative resistant kernels and factorial Least‐Cost Paths (fLCP) in two complementary approaches: core area‐based and PA‐based connectivity. We identified 307 core areas for jaguar movement, covering ~7.75 million km 2 (55% of the current range), of which approximately half lies within PAs. The largest and highest‐ranked core area spans ~6.5 million km 2 across four biomes (Amazon, Llanos, Chaco and Pantanal). We identified 176 dispersal corridors connecting core areas, although connectivity was not continuous across the entire range. Northern populations (Mexico and Central America) showed several connectivity gaps, whereas South America displayed a large, highly interconnected network linking the Amazon, Llanos, Chaco, Pantanal, Cerrado, Caatinga, Iberá and the Atlantic Forest's Green Corridor. In contrast, coastal Atlantic Forest patches appeared largely isolated. The PA‐based analysis predicted 507 potential corridors connecting 905 PAs, including potential links absent from the core area model, particularly across Central America and between the Darién Gap, Amazon and coastal Atlantic Forest. The core‐area approach provides a more biologically realistic representation of current connectivity, while the PA‐based approach complements it by identifying pragmatic opportunities for long‐term connectivity conservation. Together, these approaches identify priority areas and regions of uncertainty, providing a spatial framework to guide jaguar conservation and connectivity planning under accelerating global change.

Integrated modelling reveals widespread distribution of invasive wild pigs across Australia - Matthew W. Rees; David J. Mitchell; Katherina Ng; Sandra K. Parsons; Kirstin M. Proft; Scott D. Foster; David Peel; Zachary Amir; Tom Bruce; Matthew S. Luskin; Jens G. Froese (Biological Conservation, 2026)

A quantitative comparison of tools for monitoring the abundance of crown-of-thorns starfish and coral cover - Emma Lawrence; Scott D. Foster; Samuel A. Matthews; David Williamson; Morgan S. Pratchett; Jason Doyle; Scott Bainbridge; Sven Uthicke; Peter C. Doll; Brano Kusy; Mohammad A. Armin; Mary C. Bonin (Coral Reefs, 2026)
Effective monitoring of crown-of-thorns starfish (COTS) populations and coral cover is critical for informing management of COTS outbreaks throughout their tropical Indo-Pacific range, including Australia’s Great Barrier Reef. However, existing monitoring tools such as manta tow and cull diver surveys have well-known limitations including accuracy and resource demands. This study evaluates a range of monitoring tools for assessing both COTS and coral populations. Tools that measure both COTS and coral include manta tow surveys, scooter-assisted large area diver-based (SALAD) surveys and surveys undertaken using the ReefScan towed camera platform. For COTS-only monitoring, we examine cull diver surveys and environmental DNA (eDNA) sampling. Data from side-by-side deployments on seven to ten reefs (depending on the tool) with varying COTS densities and coral cover were collected and analysed to calibrate estimates between tools. The calibration models developed will aid in integrating data from diverse sources and facilitate the translation of estimates based on one monitoring tool to another. Critically, the models provide a means of estimating COTS density (COTS per hectare) for monitoring tools that do not directly collect this measure, allowing more meaningful decision-making around ecological thresholds and enabling threshold-based management regardless of which tool collected the data. The study emphasises that each tool has specific applications for addressing knowledge gaps and informing management decisions, advocating for an integrated, multi-tool monitoring strategy that leverages the strengths of each tool to improve the overall effectiveness and efficiency of COTS and coral monitoring.

An interactive tool to identify existing evidence and research gaps on agricultural production processes to address heavy metals in foods: developed from a scoping review - Rupal Trivedi; Lauren E. O’Connor; Cassi N. Leta; Trish J. Bosse; Julie S. Davis; Arin A. Balalian; Rachel C. Thoerig; Shailesh M. Advani; Margaret J. Foster; Kyle M. Holland; David D. Baltensperger; Delbert M. Gatlin III; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Groundwater-based water services as complex socio-hydrogeological systems: insights from Vietnam’s Mekong Delta - Naomi Carrard; Diana Gonzalez; Jess MacArthur; Nguyen Anh Minh; Nguyen Dinh Giang Nam; David Rodgers; Tim Foster (Hydrogeology Journal, 2026)
Groundwater systems are critical to global water security, yet the complex interactions between household coping strategies, resource sustainability, and climate change remain difficult to govern. This study applies qualitative systems mapping to characterise socio-hydrogeological dynamics in Vietnam’s Mekong Delta, a region currently facing intensifying saline intrusion and rapid land-use change. Drawing on a household survey ( n = 404) and in-depth interviews ( n = 25) in Sóc Trăng and Trà Vinh provinces, three critical system interactions were identified: (1) climate variability and household adaptation intensify groundwater system pressures, (2) policy-practice gaps undermine effective management of a multisource water system, and (3) social vulnerability and water stress constrain resilience. Together, these interactions illustrate how household behaviours, institutional arrangements, and resource conditions are interconnected in ways that shape system behaviour. These findings advance socio-hydrogeological frameworks by using systems mapping to make visible the relationships and interactions that influence groundwater-based water services. The research offers evidence for policymakers, suggesting that inclusive, climate-resilient service delivery depends on integrating actual household water behaviours into planning and groundwater governance, moving beyond a singular focus on piped supply.

Peripheral microRNA signature in genetic frontotemporal dementia—findings from the GENFI initiative - Chiara Fenoglio; Maria Serpente; Marina Arcaro; Tiziana Carandini; Luca Sacchi; Manuela Pintus; Vittoria Borracci; Giulia Giudici; Marta Rigoni; Paola Muti; Laura Ghezzi; Arabella Bouzigues; et al. (GeroScience, 2026)
Frontotemporal dementia (FTD) is a neurodegenerative disease characterized by significant clinical and genetic heterogeneity, with approximately 40% of cases linked to hereditary genetic mutations, including MAPT , GRN , and C9ORF72 . Recently, microRNAs (miRNAs) have emerged as key regulators of cellular processes related to neurodegeneration and as potential biomarkers for FTD. However, their relevance in presymptomatic stages remains poorly understood. We conducted a miRNA expression analysis using TaqMan OpenArray® panels on blood samples collected from 171 individuals, including symptomatic mutation carriers (SMC), presymptomatic carriers (PMC), and healthy non-carriers (NC). Dysregulated miRNAs were validated and bioinformatic tools were used to identify potential associated molecular pathways. In C9ORF72 , miR-20b-5p and miR-223-5p were significantly upregulated in SMC (fold regulation over NC: 2.418 p = 0.0336 and 7.829 p < 0.0264 respectively) and PMC (5.518, p < 0.0001 and 3.941, p < 0.0001 respectively). In GRN mutation carriers, miR-28-3p was altered in both SMC and PMC (fold regulation over NC: 1.484 p < 0.050 and 3.287, p < 0.050). In MAPT mutation carriers, miR-28-5p, miR-192-3p, miR-25-3p, and miR-532-3p were altered only in SMC (fold regulation over NC: 1.496 p < 0.050, 1.911 p = 0.006, 1.468 p < 0.05, and 0.728 p < 0.05). Bioinformatic analysis revealed enrichment of pathways related to neurodegeneration and synapse impairment. These results suggest that miRNA expression levels are deregulated in mutated SMC, in C9ORF72 and GRN PMC. Notably, miR-20b-5p, miR-223-5p, and miR-28-3p were increased in preclinical stages of the disease, supporting their role as early biomarkers for C9ORF72 -FTD and GRN -FTD. Conversely, alterations in MAPT carriers appeared only in symptomatic stages, suggesting a different involvement in disease progression.

Spatiotemporal soil fertility responses to enhanced rock weathering along a hillslope catena within a temperate, agricultural watershed - Quinn C. Zacharias; Robert Rioux; Fengchao Sun; Wyatt Tatge; Evelin Pihlap; Emmanuel Nyavor; David A. Foster; Joshua L. Warren; Mark A. Bradford; Peter Raymond; Noah Planavsky; James Saiers (Nutrient Cycling in Agroecosystems, 2026)

Simulation of recurring defoliation by multiple insects shows lasting consequences for carbon storage in temperate oak forests - Jane R. Foster; Robert M. Scheller; Brian R. Sturtevant; Philip A. Townsend; Brian Miranda; David J. Mladenoff (Forest Ecology and Management, 2026)

Morrittospora corbiculae n. gen. n. sp., a microsporidian parasite infecting the invasive Asian clam Corbicula fluminea from the River Thames, London - Rachel Foster; Kelly S. Bateman; Paul F. Clark; Matthew J. Green; Chantelle Hooper; Stuart H. Ross; Paul Stebbing; Georgia M. Ward; David Bass (Journal of Invertebrate Pathology, 2026)

Development of new global lake brGDGT-temperature calibrations: advances, applications, challenges, and recommendations - Emma J. Pearson; Steve Juggins; Harry Allbrook; Louise C. Foster; Dominic A. Hodgson; B. David A. Naafs; Tony Phillips; Stephen J. Roberts (Quaternary Science Reviews, 2025)

Educational and Equity Implications of Biomarker Testing and Targeted Therapy Access in NSCLC: Insights from the NIH All of Us Research Program - Patrick J. Kiel; Todd C. Skaar; David R. Foster; Karen Suchanek Hudmon; Michael A. Preston (Journal of Cancer Education, 2025)
Precision oncology in non-small cell lung cancer (NSCLC) depends on biomarker testing and access to targeted therapies. However, disparities in testing and treatment highlight critical educational needs for patients, providers, and health systems. Using the NIH All of Us Research Program (2017–2022), we identified 287 patients with advanced NSCLC who received first-line carboplatin-based chemotherapy or targeted therapy. Social determinants of health (SDoH) including education, employment, retirement, and disability were evaluated as predictors of biomarker testing and targeted therapy receipt. Only 18% of patients had documented biomarker testing despite 45% minority representation in the All of Us cohort. Patients with any college education had significantly higher odds of receiving targeted therapy (OR 2.43, 95% CI 1.23–4.97), while retired patients were less likely to receive targeted therapy (OR 0.35, 95% CI 0.18–0.68). Disability was associated with increased biomarker testing (OR 2.82, 95% CI 1.19–6.51). Although TTD was longer for targeted therapies, incomplete biomarker documentation limited interpretation of outcomes. Findings underscore the need for enhanced cancer education strategies to improve biomarker literacy, guideline adherence, and equitable access to targeted therapy. Educational outreach should focus on retirees and patients with lower educational attainment, while provider training and system-level improvements are needed to strengthen precision oncology delivery.

Challenges and Strategic Recommendations for Enhancing Quantification and Projection of Forest Carbon Dynamics - Holly L. Munro; Christopher W. Woodall; William R. L. Anderegg; Jeff W. Atkins; Colin M. Beier; Bronson P. Bullock; Kendall DeLyser; David D. Diaz; Bianca N.I. Eskelson; Margaret E. K. Evans; John D. Foppert; Bryan C. Foster; et al. (Journal of Forestry, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Speech Treatment for People with Cerebellar Multiple System Atrophy (MSA-C): A Pilot Randomised Controlled Trial of Two Approaches - Anja Lowit; Kaiyue Xing; D. Priya Shanmugarajah; Emma Foster; Suzanna Duty; David Young; Jan Stanier; Christopher Kobylecki; Marios Hadjivassiliou (The Cerebellum, 2025)
Speech problems are an early feature of Multiple System Atrophy (MSA). They can lead to social withdrawal and have significant impact on people’s quality of life. There is a considerable lack of clinical trials and clinicians lack guidance on how best to support this population. This project aimed to establish the feasibility and acceptability of a novel treatment approach, ClearSpeechTogether, in patients with the cerebellar variant of MSA (MSA-C), and to pilot an RCT comparing this treatment to standard speech and language therapy (SLT) treatment (ST). We recruited 24 patients with clinically probable MSA-C and dysarthria who were randomised to either treatment arm. Full data were available for 9 participants for ST, and 11 for ClearSpeechTogether. Both interventions lasted 6 weeks, ST offered 1 h of individual therapy a week, ClearSpeechTogether provided four individual therapy sessions over two weeks, followed by four weeks of daily, patient led group practice. Assessment and intervention were provided online via videoconferencing software. Data collection focused on feasibility, acceptability and signal of efficacy. Recruitment, conversion and attrition rates were within or close to target, and neither participants nor clinicians highlighted any acceptability issues. Communication outcomes were mixed, with biggest gains made in communication confidence and participation across both groups. Rapid decline in overall health status appeared to have impacted results. Results were generally positive and support the implementation of larger follow up trials. The study also demonstrated that people with MSA-C can benefit from speech therapy even at more severe stages of their disease progression.

Societal value of seagrass from historical to contemporary perspectives - Nicole R. Foster; Eugenia T. Apostolaki; Katelyn DiBenedetto; Carlos M. Duarte; David Gregory; Karina Inostroza; Dorte Krause-Jensen; Benjamin L. H. Jones; Eduard Serrano; Rym Zakhama-Sraieb; Oscar Serrano (Ambio, 2025)
Seagrasses have been entwined with human culture for millennia, constituting a natural resource that has supported humanity throughout this history. Understanding the societal value of seagrass fosters appreciation of these ecosystems, encouraging conservation and restoration actions to counteract historic and predicted losses. This study overviews the plethora of seagrass use in human history, ranging from spiritual and ceremonial roles, direct and indirect food resources, medicines and raw materials, dating back more than 180 000 years. While many past uses have been abandoned in modern societies, others have persisted or are being rediscovered, and new applications are emerging. As these uses of seagrasses depend on harvesting, we also underscore the need for sustainable practices to (re)generate positive interactions between seagrasses and society. Our review contributes to revalue seagrass societal ecosystem services, highlighting ancient and more recent human and seagrass relationships to incentivize conservation and restoration actions.

Qualitative risk analysis of invasive pathogens spreading via raw water transfers in the UK - Rachel Foster; David Bass; Paul F. Clark; David Morritt; Paul Stebbing (Science of The Total Environment, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

When can we detect lianas from space? Toward a mechanistic understanding of liana‐infested forest optics - Marco D. Visser; Matteo Detto; Félicien Meunier; Jin Wu; Jane R. Foster; David C. Marvin; Peter M. van Bodegom; Boris Bongalov; Matheus Henrique Nunes; David Coomes; Hans Verbeeck; J. Antonio Guzmán Q; et al. (Ecology, 2025)
Lianas, woody vines acting as structural parasites of trees, have profound effects on the composition and structure of tropical forests, impacting tree growth, mortality, and forest succession. Remote sensing could offer a powerful tool for quantifying the scale of liana infestation, provided the availability of robust detection methods. We analyze the consistency and global geographic specificity of spectral signals—reflectance across wavelengths—from liana‐infested tree crowns and forest stands, examining the underlying mechanisms of these signals. We compiled a uniquely comprehensive database, including leaf reflectance spectra from 5424 leaves, fine‐scale airborne reflectance data from 999 liana‐infested canopies, and coarse‐scale satellite reflectance data covering 775 ha of liana‐infested forest stands. To unravel the mechanisms of the liana spectral signal, we applied mechanistic radiative transfer models across scales, establishing a synthesis of the relative importance of different mechanisms, which we corroborate with field data on liana leaf chemistry and canopy structure. We find a consistent liana spectral signal at canopy and stand scales across globally distributed sites. This signature mainly arises at the canopy level due to direct effects of more horizontal leaf angles, resulting in a larger projected leaf area, and indirect effects from increased light scattering in the near and short‐wave infrared regions, linked to lianas' less costly leaf construction compared with trees on average. The existence of a consistent global spectral signal for lianas suggests that large‐scale quantification of liana infestation is feasible. However, because the traits responsible for the liana canopy‐reflectance signal are not exclusive to lianas, accurate large‐scale detection requires rigorously validated remote sensing methods. Our models highlight challenges in automated detection, such as potential misidentification due to leaf phenology, tree life history, topography, and climate, especially where the scale of liana infestation is less than a single remote sensing pixel. The observed cross‐site patterns also prompt ecological questions about lianas' adaptive similarities in optical traits across environments, indicating possible convergent evolution due to shared constraints on leaf biochemical and structural traits.

Current state of plant conservation translocations across Europe: motivations, challenges and outcomes - Sandrine Godefroid; Sam Lacquaye; Andreas Ensslin; Sarah Dalrymple; Thomas Abeli; Hannah Branwood; Inmaculada Ferrando Pardo; P. Pablo Ferrer Gallego; Elke Zippel; Luísa Gouveia; Carlos Alberto Lobo; Francisco Fernandes; et al. (Biodiversity and Conservation, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

The Coastal Ocean Environment Summer School In Nigeria and Ghana: The Value of Long-Term, Sustained Capacity Sharing - Brian Arbic; Johnson Adjetey; Andrews Agyekumhene; Mosunmola Akinwunmi; Lailah Akita; Lois Anderson; Joseph Ansong; Kwasi Appeaning Addo; Eunice Asamoah; Olawale Awe; Christian Buckingham; Janae’ Collier; et al. (Oceanography, 2025)
The Coastal Ocean Environment Summer School In Nigeria and Ghana (COESSING; https://coessing.org) has been run for one week every year since 2015. The school, an endorsed project of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030), has provided a platform for approximately 1,000 scientists from Africa, the United States, and Europe to exchange scientific knowledge, to network, to learn, and to collaborate. Our interdisciplinary, multicultural, and multi-institutional approach offers a model for knowledge exchange across the globe and across different educational levels.

2D geochemical imaging of biogenic marine carbonates using LA-TOF-ICP-MS at 1 and 2 μm pixel resolution - Christopher D. Standish; J. Andy Milton; Tessa M. Page; Rachel M. Brown; David Douglas; Bence Paul; Lukas Schlatt; Gavin L. Foster (Chemical Geology, 2024)

Controls on sediment transport from rivers to trenches in passive and active continental margins - Letian Zeng; Ce Wang; David A. Foster; Ming Su; Heqi Cui; Junmin Jia (Science China Earth Sciences, 2024)

Correction: Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)

Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)
Female Weddell seals ( Leptonychotes weddellii ) display a mixed capital-income breeding strategy, losing up to 40% of their body mass between birthing and weaning their pups. How and when they regain energy stores, however, remains to be fully explored. To better understand the foraging by lactating Weddell seals, we fitted time-depth recorders and head-mounted cameras on 26 seals in Erebus Bay, Ross Sea, for ~ 5 days in November and December 2018 and 2019. We aimed to (1) identify prey species and foraging depth and (2) investigate relationships between seal physiology and demographics and probability of foraging. We recorded 2782 dives, 903 of which were > 50 m, maximum depth was 449.3 m and maximum duration was 31.1 min. Pup age likely contributes to the probability of a lactating Weddell seal foraging (Est. = 1.21 (SD = 0.61), z = 1.97, p = 0.0484). Among 846 prey encounters, the most frequent prey items were crustaceans (46.2%) and Antarctic silverfish ( Pleuragramma antarcticum , 19.0%); two encounters were observed with juvenile Antarctic toothfish ( Dissostichus mawsoni , 0.2%). We identified substantial variability in foraging behaviour, individually and between locations, and found that lactating seals target many species and some may specialise on certain prey groups.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Cerebellum and basal ganglia connectivity in isolated REM sleep behaviour disorder and Parkinson’s disease: an exploratory study - Michael J. Firbank; Jacopo Pasquini; Laura Best; Victoria Foster; Hilmar P. Sigurdsson; Kirstie N. Anderson; George Petrides; David J. Brooks; Nicola Pavese (Brain Imaging and Behavior, 2024)
REM sleep behaviour disorder (RBD) is a parasomnia characterised by dream-enacting behaviour with loss of muscle atonia during REM sleep and is a prodromal feature of α-synucleinopathies like Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy. Although cortical-to-subcortical connectivity is well-studied in RBD, cerebellar and subcortical nuclei reciprocal connectivity is less established. Nonetheless, it could be relevant since RBD pathology involves brainstem structures with an ascending gradient. In this study, we utilised resting-state functional MRI to investigate 13 people with isolated RBD (iRBD), 17 with Parkinson’s disease and 16 healthy controls. We investigated the connectivity between the basal ganglia, thalamus and regions of the cerebellum. The cerebellum was segmented using a functional atlas, defined by a resting-state network-based parcellation, rather than an anatomical one. Controlling for age, we found a significant group difference (F 4,82 = 5.47, p FDR = 0.017) in cerebellar-thalamic connectivity, with iRBD significantly lower compared to both control and Parkinson’s disease. Specifically, cerebellar areas involved in this connectivity reduction were related to the default mode, language and fronto-parietal resting-state networks. Our findings show functional connectivity abnormalities in subcortical structures that are specific to iRBD and may be relevant from a pathophysiological standpoint. Further studies are needed to investigate how connectivity changes progress over time and whether specific changes predict disease course or phenoconversion.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Linking Taiwan to the Cathaysia Block during the Cenozoic: Evidence from Pb isotopes in detrital K-feldspar - Ce Wang; Liangjie Wei; Cheng-Shing Chiang; David A. Foster; Heqi Cui; Ming Su (Global and Planetary Change, 2024)

Tectonic evolution of Macquarie Island: Oceanic crust, metamorphism, new-type of core complex and transpression - Ben D. Goscombe; David A. Foster; Ben Wade; Joshua J. Schwartz; Charles R. Jeffcoat (Gondwana Research, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Where does the carbon go? Long-term effects of forest management on the carbon budget of a temperate-forest water-supply watershed - David E. Foster; Peter N. Duinker; Rob C. Jamieson; Kevin Keys; James W.N. Steenberg (Journal of Environmental Management, 2024)

Scalable and sustainable manufacturing of ultrathin metal–organic framework nanosheets (MONs) for solar cell applications - David J. Ashworth; Justin Driver; Kezia Sasitharan; Ram R.R. Prasad; Joshua Nicks; Benedict J. Smith; Siddharth V. Patwardhan; Jonathan A. Foster (Chemical Engineering Journal, 2023)

Holocene provenance evolution of the northern South China Sea inferred from detrital zircon U-Pb geochronology and Hf isotopes - Ce Wang; David A. Foster; Ming Su; Yaping Lei; Letian Zeng; Heqi Cui (Global and Planetary Change, 2023)

Adaptation and mitigation capacity of wildland forests in the northeastern United States - Edward K. Faison; Danelle Laflower; Luca L. Morreale; David R. Foster; Brian Hall; Emily Johnson; Jonathan R. Thompson (Forest Ecology and Management, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Biomechanical Properties of Knee Medial Collateral Ligament Compared to Palmaris Longus for Ulnar Collateral Ligament Reconstruction - Dave Huang; Lukas Foster; Michael Stone; David Kulber; Melodie F. Metzger (Annals of Biomedical Engineering, 2023)
Ulnar collateral ligament reconstruction (UCLR) is frequently performed among injured overhead-throwing athletes. One of the most common graft choices when performing a UCLR is the ipsilateral palmaris longus tendon (PL). The purpose of this study was to investigate the material properties of aseptically processed cadaveric knee collateral ligaments (kMCL) as a potential graft source for UCLR and compare them to the gold standard PL autograft. Each PL and kMCL cadaveric sample was subjected to cyclic preconditioning, stress relaxation, and load-to-failure testing, and the mechanical properties were recorded. PL samples exhibited a greater average decrease in stress compared to the kMCL samples during the stress-relaxation test ( p p p = 0.03 and 0.02, respectively. Both graft materials had comparable maximum toughness and demonstrated a similar ability to deform plastically without rupture. The clinical significance of our result is that prepared knee medial collateral ligament allografts may provide a viable graft material for use in the reconstruction of elbow ligaments.

Temporal dynamics of soil fungi in a pyrodiverse dry‐sclerophyll forest - Elle J. Bowd; Eleonora Egidi; David B. Lindenmayer; David A. Wardle; Paul Kardol; Claire Foster (Molecular Ecology, 2023)
Fire is a major evolutionary and ecological driver that shapes biodiversity in forests. While above‐ground community responses to fire have been well‐documented, those below‐ground are much less understood. However, below‐ground communities, including fungi, play key roles in forests and facilitate the recovery of other organisms after fire. Here, we used internal transcribed spacer (ITS) meta‐barcoding data from forests with three different times since fire [short (3 years), medium (13–19 years) and long (>26 years)] to characterize the temporal responses of soil fungal communities across functional groups, ectomycorrhizal exploration strategies and inter‐guild associations. Our findings indicate that fire effects on fungal communities are strongest in the short to medium term, with clear distinctions between communities in forests with a short time (3 years) since fire, a medium time (13–19 years) and a long time (>26 years) since fire. Ectomycorrhizal fungi were disproportionately impacted by fire relative to saprotrophs, but the direction of the response varied depending on morphological structures and exploration strategies. For instance, short‐distance ectomycorrhizal fungi increased with recent fire, while medium‐distance (fringe) ectomycorrhizal fungi decreased. Further, we detected strong, negative inter‐guild associations between ectomycorrhizal and saprotrophic fungi but only at medium and long times since fire. Given the functional significance of fungi, the temporal changes in fungal composition, inter‐guild associations and functional groups after fire demonstrated in our study may have functional implications that require adaptive management to curtail.

Surface displacement expression of progressive failure in a sensitive clay landslide observed with long-term UAV monitoring - Michael J. Bentley; Jonathan M. Foster; Joshua J. Potvin; George Bevan; James Sharp; David J. Woeller; W. Andy Take (Landslides, 2023)

Radiosensitivity and Biological Effects of Gamma and X-Rays on Germination and Seedling Vigour of Three Coffea arabica Varieties - Keji Emmanuel Dada; David Adedayo Animasaun; Oba Toyin Mustapha; Souleymane Bado; Brian P. Foster (Journal of Plant Growth Regulation, 2023)

Variant-specific SARS-CoV-2 shedding rates in wastewater - Sarah M. Prasek; Ian L. Pepper; Gabriel K. Innes; Stephanie Slinski; Walter Q. Betancourt; Aidan R. Foster; Hayley D. Yaglom; W. Tanner Porter; David M. Engelthaler; Bradley W. Schmitz (Science of The Total Environment, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Systemic review of genetic and epigenetic factors underlying differential toxicity to environmental lead (Pb) exposure - Danila Cuomo; Margaret J. Foster; David Threadgill (Environmental Science and Pollution Research, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Correction to: Late Neogene evolution of the Peruvian margin and its ecosystems: a synthesis from the Sacaco record - Diana Ochoa; Rodolfo Salas-Gismondi; Thomas J. DeVries; Patrice Baby; Christian de Muizon; Alí Altamirano; Angel Barbosa-Espitia; David A. Foster; Kelly Quispe; Jorge Cardich; Dimitri Gutiérrez; Alexander Perez; et al. (International Journal of Earth Sciences, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

RGS14 modulates locomotor behavior and ERK signaling induced by environmental novelty and cocaine within discrete limbic structures - Stephanie L. Foster; Daniel J. Lustberg; Nicholas H. Harbin; Sara N. Bramlett; John R. Hepler; David Weinshenker (Psychopharmacology, 2021)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Late Neogene evolution of the Peruvian margin and its ecosystems: a synthesis from the Sacaco record - Diana Ochoa; Rodolfo Salas-Gismondi; Thomas J. DeVries; Patrice Baby; Christian de Muizon; Alí Altamirano; Angel Barbosa-Espitia; David A. Foster; Kelly Quispe; Jorge Cardich; Dimitri Gutiérrez; Alexander Perez; et al. (International Journal of Earth Sciences, 2021)
The highly productive waters of the Humboldt Current System (HCS) host a particular temperate ecosystem within the tropics, whose history is still largely unknown. The Pisco Formation, deposited during Mio-Pliocene times in the Peruvian continental margin has yielded an outstanding collection of coastal-marine fossils, providing an opportunity to understand the genesis of the HCS ecosystem. We present a comprehensive review, completed with new results, that integrates geological and paleontological data from the last 10 My, especially focusing on the southern East Pisco Basin (Sacaco area). We discuss the depositional settings of the Pisco Formation and integrate new U/Pb radiometric ages into the chronostratigraphic framework of the Sacaco sub-basin. The last preserved Pisco sediments at Sacaco were deposited ~ 4.5 Ma, while the overlying Caracoles Formation accumulated from ~ 2.7 Ma onwards. We identified a Pliocene angular unconformity encompassing 1.7 My between these formations, associated with a regional phase of uplift. Local and regional paleoenvironmental indicators suggest that shallow settings influenced by the offshore upwelling of ventilated and warm waters prevailed until the early Pliocene. We present an extensive synthesis of the late Miocene–Pleistocene vertebrate fossil record, which allows for an ecological characterization of the coastal-marine communities, an assessment of biodiversity trends, and changes in coastal-marine lineages in relation to modern HCS faunas. Our synthesis shows that: (i) typical endemic coastal Pisco vertebrates persisted up to ~ 4.5 Ma, (ii) first modern HCS toothed cetaceans appear at ~ 7–6 Ma, coinciding with a decline in genus diversity, and (iii) a vertebrate community closer to the current HCS was only reached after 2.7 Ma. The genesis of the Peruvian coastal ecosystem seems to be driven by a combination of stepwise transformations of the coastal geomorphology related to local tectonic pulses and by a global cooling trend leading to the modern oceanic circulation system.

Effects of plant functional group removal on CO 2 fluxes and belowground C stocks across contrasting ecosystems - Roger Grau‐Andrés; David A. Wardle; Michael J. Gundale; Claire N. Foster; Paul Kardol (Ecology, 2020)
Changes in plant communities can have large effects on ecosystem carbon (C) dynamics and long‐term C stocks. However, how these effects are mediated by environmental context or vary among ecosystems is not well understood. To study this, we used a long‐term plant removal experiment set up across 30 forested lake islands in northern Sweden that collectively represent a strong gradient of soil fertility and ecosystem productivity. We measured forest floor CO 2 exchange and aboveground and belowground C stocks for a 22‐yr experiment involving factorial removal of the two dominant functional groups of the boreal forest understory, namely ericaceous dwarf shrubs and feather mosses, on each of the 30 islands. We found that long‐term shrub and moss removal increased forest floor net CO 2 loss and decreased belowground C stocks consistently across the islands irrespective of their productivity or soil fertility. However, we did see context‐dependent responses of respiration to shrub removals because removals only increased respiration on islands of intermediate productivity. Both CO 2 exchange and C stocks responded more strongly to shrub removal than to moss removal. Shrub removal reduced gross primary productivity of the forest floor consistently across the island gradient, but it had no effect on respiration, which suggests that loss of belowground C caused by the removals was driven by reduced litter inputs. Across the island gradient, shrub removal consistently depleted C stocks in the soil organic horizon by 0.8 kg C/m 2 . Our results show that the effect of plant functional group diversity on C dynamics can be relatively consistent across contrasting ecosystems that vary greatly in productivity and soil fertility. These findings underline the key role of understory vegetation in forest C cycling, and suggest that global change leading to changes in the relative abundance of both shrubs and mosses could impact on the capacity of boreal forests to store C.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Contribution of NDM and OXA-type carbapenemases to carbapenem resistance in clinical Acinetobacter baumannii from Nigeria - David O. Ogbolu; Oyebode A. Terry Alli; Adeolu S. Oluremi; Y. Temilola Ogunjimi; D. Iyanu Ojebode; Veronica Dada; Olubunmi O. Alaka; Ebenezer Foster-Nyarko; Mark A. Webber (Infectious Diseases, 2020)

Demonstrating Contribution of Components of Fixed-Dose Drug Combinations Through Longitudinal Exposure-Response Analysis - Asbjørn Nøhr-Nielsen; Theis Lange; Julie Lyng Forman; Theodoros Papathanasiou; David J. R. Foster; Richard N. Upton; Ole Jannik Bjerrum; Trine Meldgaard Lund (The AAPS Journal, 2020)

Genomics detects population structure within and between ocean basins in a circumpolar seabird: The white‐chinned petrel - Kalinka Rexer‐Huber; Andrew J. Veale; Paulo Catry; Yves Cherel; Ludovic Dutoit; Yasmin Foster; John C. McEwan; Graham C. Parker; Richard A. Phillips; Peter G. Ryan; Andrew J. Stanworth; Tracey van Stijn; et al. (Molecular Ecology, 2019)
The Southern Ocean represents a continuous stretch of circumpolar marine habitat, but the potential physical and ecological drivers of evolutionary genetic differentiation across this vast ecosystem remain unclear. We tested for genetic structure across the full circumpolar range of the white‐chinned petrel ( Procellaria aequinoctialis ) to unravel the potential drivers of population differentiation and test alternative population differentiation hypotheses. Following range‐wide comprehensive sampling, we applied genomic (genotyping‐by‐sequencing or GBS; 60,709 loci) and standard mitochondrial‐marker approaches (cytochrome b and first domain of control region) to quantify genetic diversity within and among island populations, test for isolation by distance, and quantify the number of genetic clusters using neutral and outlier (non‐neutral) loci. Our results supported the multi‐region hypothesis, with a range of analyses showing clear three‐region genetic population structure, split by ocean basin, within two evolutionary units. The most significant differentiation between these regions confirmed previous work distinguishing New Zealand and nominate subspecies. Although there was little evidence of structure within the island groups of the Indian or Atlantic oceans, a small set of highly‐discriminatory outlier loci could assign petrels to ocean basin and potentially to island group, though the latter needs further verification. Genomic data hold the key to revealing substantial regional genetic structure within wide‐ranging circumpolar species previously assumed to be panmictic.

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

Monitoring forest cover change within different reserve types in southern Ghana - Yu Hsin Tsai; Douglas A. Stow; David López-Carr; John R. Weeks; Keith C. Clarke; Foster Mensah (Environmental Monitoring and Assessment, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Weather effects on birds of different size are mediated by long‐term climate and vegetation type in endangered temperate woodlands - David B. Lindenmayer; Peter Lane; Mason Crane; Daniel Florance; Claire N. Foster; Karen Ikin; Damian Michael; Chloe F. Sato; Ben C. Scheele; Martin J. Westgate (Global Change Biology, 2019)
Species occurrence is influenced by a range of factors including habitat attributes, climate, weather, and human landscape modification. These drivers are likely to interact, but their effects are frequently quantified independently. Here, we report the results of a 13‐year study of temperate woodland birds in south‐eastern Australia to quantify how different‐sized birds respond to the interacting effects of: (a) short‐term weather (rainfall and temperature in the 12 months preceding our surveys), (b) long‐term climate (average rainfall and maximum and minimum temperatures over the period 1970–2014), and (c) broad structural forms of vegetation (old‐growth woodland, regrowth woodland, and restoration plantings). We uncovered significant interactions between bird body size, vegetation type, climate, and weather. High short‐term rainfall was associated with decreased occurrence of large birds in old‐growth and regrowth woodland, but not in restoration plantings. Conversely, small bird occurrence peaked in wet years, but this effect was most pronounced in locations with a history of high rainfall, and was actually reversed (peak occurrence in dry years) in restoration plantings in dry climates. The occurrence of small birds was depressed—and large birds elevated—in hot years, except in restoration plantings which supported few large birds under these circumstances. Our investigation suggests that different mechanisms may underpin contrasting responses of small and large birds to the interacting effects of climate, weather, and vegetation type. A diversity of vegetation cover is needed across a landscape to promote the occurrence of different‐sized bird species in agriculture‐dominated landscapes, particularly under variable weather conditions. Climate change is predicted to lead to widespread drying of our study region, and restoration plantings—especially currently climatically wet areas—may become critically important for conserving bird species, particularly small‐bodied taxa.

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

A holistic investigation of the ecological correlates of abundance and body size for the endangered White's seahorse Hippocampus whitei - Clayton G. Manning; Sarah J. Foster; David Harasti; Amanda C. J. Vincent (Journal of Fish Biology, 2018)
Analysing the associations between the endangered White's seahorse Hippocampus whitei and characteristics of its environment (including habitat, prey and predator variables) in an estuary in New South Wales, Australia, revealed that seahorses had a greater number of significant associations with environmental correlates within a single seagrass bed than among seagrass beds. Predator abundance was negatively correlated with H. whitei abundances among seven seagrass beds (200–6,000 m apart) and no ecological correlate was associated with H. whitei body size distributions. Within the seagrass bed with the greatest number of H. whitei , individuals preferentially selected locations that were deeper, had denser seagrass, more epiphytic prey types and fewer predators. Smaller H. whitei were associated with greater depths within the bed. In this study, each class of ecological correlate (habitat, prey, predators) was found to have at least one significant relationship with H. whitei , depending on the scale, demonstrating that all three are important to H. whitei populations. As such, future studies that evaluate animal populations may benefit from holistic approaches that consider each of these together. For animals that are experiencing dramatic population declines due to habitat destruction, as H. whitei has over the last decade, a better understanding of its relationship to its environment is important to inform conservation action.

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

Correction to: Polarisation vision: overcoming challenges of working with a property of light we barely see - James J. Foster; Shelby E. Temple; Martin J. How; Ilse M. Daly; Camilla R. Sharkey; David Wilby; Nicholas W. Roberts (The Science of Nature, 2018)

Catch rate and at‐vessel mortality of circle hooks versus J‐hooks in pelagic longline fisheries: A global meta‐analysis - James F. Reinhardt; Jennifer Weaver; Pamela J. Latham; Andrea Dell'Apa; Joseph E. Serafy; Joan A. Browder; Mary Christman; Daniel G. Foster; David R. Blankinship (Fish and Fisheries, 2018)
We conducted a meta‐analysis of literature reporting on the use of circle hooks and J‐hooks in pelagic longline fisheries. Our study included more data than previous meta‐analyses of the effects of hook type, due to both a larger number of relevant studies available in recent years and a more general modelling approach. Data from 42 empirical studies were analysed using a random effects model to compare the effects of circle hooks and J‐hooks on catch rate (43 species) and at‐vessel mortality (31 species) of target and bycatch species. Catch rates with circle hooks were greater for 11 species, including four tuna species, six shark species and one Istiophorid billfish. Catch rates on circle hooks were lower for seven species, including two Istiophorid billfishes and two species of sea turtle. At‐vessel mortality was significantly lower with circle hooks in 12 species, including three tuna species, three Istiophorid billfishes, swordfish ( Xiphias gladius ) and three shark species. No species had significantly greater at‐vessel mortality when captured with a circle hook rather than a J‐hook. While our general approach increased model variability compared to more detailed studies, results were consistent with trends identified in previous studies that compared the catch rates and at‐vessel mortality (between hook types) for a number of species. Our results suggest that circle hooks can be a promising tool to reduce mortality of some bycatch species in pelagic longline fisheries, although the effects depend on the species and the metric (catch rate or at‐vessel mortality), emphasizing the need for fishery‐specific data in conservation and management decisions.

Polarisation vision: overcoming challenges of working with a property of light we barely see - James J. Foster; Shelby E. Temple; Martin J. How; Ilse M. Daly; Camilla R. Sharkey; David Wilby; Nicholas W. Roberts (The Science of Nature, 2018)

Population in vitro–in vivo pharmacokinetic model of first-pass metabolism: itraconazole and hydroxy-itraconazole - Ahmad Y. Abuhelwa; Stuart Mudge; Richard N. Upton; David J. R. Foster (Journal of Pharmacokinetics and Pharmacodynamics, 2018)

Simultaneous vegetation classification and mapping at large spatial scales - Mitchell B. Lyons; Scott D. Foster; David A. Keith (Journal of Biogeography, 2017)
Aim Multivariate mixture models offer the ability to streamline the typically multi‐stage process of vegetation classification and mapping into a single, simultaneous analytical step. Our aim is to demonstrate the model's utility over large and diverse areas, with comparison to existing classification and mapping conventions. Location New South Wales, Australia. Methods We demonstrate a statistical model that uses both multivariate species data and environmental covariate data to simultaneously classify observations into groups and predict those groups out into environmental and geographical space. We used two large data sets to demonstrate the method: an ~810,000 km 2 area with 4,715 sites and 488 species and a ~220,000 km 2 area with 5,183 sites and 446 species. A range of topographic, terrain, climate and soil predictors were used as environmental variables, including future projected climate variables. Models can be fit with the R package “ RCP mod.” Results The method results in probabilistic memberships to vegetation assemblages, for both the classification and map. There was general agreement between our approach and existing vegetation classification conventions, but we explore some notable differences. We were able to examine the environmental gradients that define the predicted vegetation distributions, as well as make predictions about how the distribution of species assemblages might shift as a result of climate change. Main conclusions Our approach tightens the link between description of biodiversity patterns and their depiction in space, by considering both biotic and spatially explicit abiotic information simultaneously. The method allows uncertainty to be quantified objectively across a consistent set of groups for both vegetation classification and mapping, which is rarely the case in traditional multi‐stage approaches. A simultaneous modelling approach increases capacity to make predictions into varying spatial, temporal and environmental dimensions, providing new ecological insights and increasing capacity for evidence‐based decision making.

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Infliximab Maintenance Dosing in Inflammatory Bowel Disease: an Example for In Silico Assessment of Adaptive Dosing Strategies - Jessica Wojciechowski; Richard N. Upton; Diane R. Mould; Michael D. Wiese; David J. R. Foster (The AAPS Journal, 2017)

Quantitative trait loci controlling vegetative propagation traits mapped in European pear (Pyrus communis L.) - Mareike Knäbel; Adam P. Friend; John W. Palmer; Robert Diack; Susan E. Gardiner; Stuart Tustin; Robert Schaffer; Toshi Foster; David Chagné (Tree Genetics & Genomes, 2017)

Comparison of non-compartmental and mixed effect modelling methods for establishing bioequivalence for the case of two compartment kinetics and censored concentrations - Jim H. Hughes; Richard N. Upton; David J. R. Foster (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Historic grazing in southern New England, USA, recorded by fungal spores in lake sediments - Maria E. Orbay-Cerrato; W. Wyatt Oswald; Elaine D. Doughty; David R. Foster; Brian R. Hall (Vegetation History and Archaeobotany, 2017)

Long‐term structural and biomass dynamics of virgin Tsuga canadensis–Pinus strobus forests after hurricane disturbance - Anthony W. D'Amato; David A. Orwig; David R. Foster; Audrey Barker Plotkin; Peter K. Schoonmaker; Maggie R. Wagner (Ecology, 2017)
The development of old‐growth forests in northeastern North America has largely been within the context of gap‐scale disturbances given the rarity of stand‐replacing disturbances. Using the 10‐ha old‐growth Harvard Tract and its associated 90‐year history of measurements, including detailed surveys in 1989 and 2009, we document the long‐term structural and biomass development of an old‐growth Tsuga canadensis–Pinus strobus forest in southern New Hampshire, USA following a stand‐replacing hurricane in 1938. Measurements of aboveground biomass pools were integrated with data from second‐ and old‐growth T. canadensis forests to evaluate long‐term patterns in biomass development following this disturbance. Ecosystem structure across the Tract prior to the hurricane exhibited a high degree of spatial heterogeneity with the greatest levels of live tree basal area (70–129 m 2 /ha) on upper west‐facing slopes where P. strobus was dominant and intermixed with T. canadensis . Live‐tree biomass estimates for these stratified mixtures ranged from 159 to 503 Mg/ha at the localized, plot scale (100 m 2 ) and averaged 367 Mg/ha across these portions of the landscape approaching the upper bounds for eastern forests. Live‐tree biomass 71 years after the hurricane is more uniform and lower in magnitude, with T. canadensis currently the dominant overstory tree species throughout much of the landscape. Despite only one living P. strobus stem in the 2009 plots (and fewer than five stems known across the entire 10‐ha area), the detrital legacy of this species is pronounced with localized accumulations of coarse woody debris exceeding 237.7–404.2 m 3 /ha where this species once dominated the canopy. These patterns underscore the great sizes P. strobus attained in pre‐European landscapes and its great decay resistance relative to its forest associates. Total aboveground biomass pools in this 71‐year‐old forest (255 Mg/ha) are comparable to those in modern old‐growth ecosystems in the region that also lack abundant white pine. Results highlight the importance of disturbance legacies in affecting forest structural conditions over extended periods following stand‐replacing events and underscore that post‐disturbance salvage logging can alter ecosystem development for decades. Moreover, the dominant role of old‐growth P. strobus in live and detrital biomass pools before and after the hurricane, respectively, demonstrate the disproportionate influence this species likely had on carbon storage at localized scales prior to the widespread, selective harvesting of large P. strobus across the region in the 18th and 19th centuries.

A Quantitative Review and Meta-Models of the Variability and Factors Affecting Oral Drug Absorption—Part I: Gastrointestinal pH - Ahmad Y. Abuhelwa; David J. R. Foster; Richard N. Upton (The AAPS Journal, 2016)

A Quantitative Review and Meta-models of the Variability and Factors Affecting Oral Drug Absorption—Part II: Gastrointestinal Transit Time - Ahmad Y. Abuhelwa; David J. R. Foster; Richard N. Upton (The AAPS Journal, 2016)

Effect of Gastric Fluid Volume on the In Vitro Dissolution and In Vivo Absorption of BCS Class II Drugs: a Case Study with Nifedipine - Ahmed M. Nader; Sara K. Quinney; Hala M. Fadda; David R. Foster (The AAPS Journal, 2016)

Population In Vitro-In Vivo Correlation Model Linking Gastrointestinal Transit Time, pH, and Pharmacokinetics: Itraconazole as a Model Drug - Ahmad Y. Abuhelwa; Stuart Mudge; David Hayes; Richard N. Upton; David J. R. Foster (Pharmaceutical Research, 2016)

Magmatic evolution in the N-Gondwana margin related to the opening of the Rheic Ocean—evidence from the Upper Parautochthon of the Galicia-Trás-os-Montes Zone and from the Central Iberian Zone (NW Iberian Massif) - Ícaro Dias da Silva; Rubén Díez Fernández; Alejandro Díez-Montes; Emilio González Clavijo; David A. Foster (International Journal of Earth Sciences, 2016)

The effect of high dose oral manganese exposure on copper, iron and zinc levels in rats - Courtney J. Mercadante; Carolina Herrera; Michael A. Pettiglio; Melanie L. Foster; Laura C. Johnson; David C. Dorman; Thomas B. Bartnikas (BioMetals, 2016)

Integrating theory into disturbance interaction experiments to better inform ecosystem management - Claire N. Foster; Chloe F. Sato; David B. Lindenmayer; Philip S. Barton (Global Change Biology, 2016)
Managing multiple, interacting disturbances is a key challenge to biodiversity conservation, and one that will only increase as global change drivers continue to alter disturbance regimes. Theoretical studies have highlighted the importance of a mechanistic understanding of stressor interactions for improving the prediction and management of interactive effects. However, many conservation studies are not designed or interpreted in the context of theory and instead focus on case‐specific management questions. This is a problem as it means that few studies test the relationships highlighted in theoretical models as being important for ecological management. We explore the extent of this problem among studies of interacting disturbances by reviewing recent experimental studies of the interaction between fire and grazing in terrestrial ecosystems. Interactions between fire and grazing can occur via a number of pathways; one disturbance can modify the other's likelihood, intensity or spatial distribution, or one disturbance can alter the other's impacts on individual organisms. The strength of such interactions will vary depending on disturbance attributes (e.g. size or intensity), and this variation is likely to be nonlinear. We show that few experiments testing fire–grazing interactions are able to identify the mechanistic pathway driving an observed interaction, and most are unable to detect nonlinear effects. We demonstrate how these limitations compromise the ability of experimental studies to effectively inform ecological management. We propose a series of adjustments to the design of disturbance interaction experiments that would enable tests of key theoretical pathways and provide the deeper ecological understanding necessary for effective management. Such considerations are relevant to studies of a broad range of ecological interactions and are critical to informing the management of disturbance regimes in the context of accelerating global change.

Global impacts of the 1980s regime shift - Philip C. Reid; Renata E. Hari; Grégory Beaugrand; David M. Livingstone; Christoph Marty; Dietmar Straile; Jonathan Barichivich; Eric Goberville; Rita Adrian; Yasuyuki Aono; Ross Brown; James Foster; et al. (Global Change Biology, 2016)
Despite evidence from a number of Earth systems that abrupt temporal changes known as regime shifts are important, their nature, scale and mechanisms remain poorly documented and understood. Applying principal component analysis, change‐point analysis and a sequential t ‐test analysis of regime shifts to 72 time series, we confirm that the 1980s regime shift represented a major change in the Earth's biophysical systems from the upper atmosphere to the depths of the ocean and from the Arctic to the Antarctic, and occurred at slightly different times around the world. Using historical climate model simulations from the Coupled Model Intercomparison Project Phase 5 ( CMIP 5) and statistical modelling of historical temperatures, we then demonstrate that this event was triggered by rapid global warming from anthropogenic plus natural forcing, the latter associated with the recovery from the El Chichón volcanic eruption. The shift in temperature that occurred at this time is hypothesized as the main forcing for a cascade of abrupt environmental changes. Within the context of the last century or more, the 1980s event was unique in terms of its global scope and scale; our observed consequences imply that if unavoidable natural events such as major volcanic eruptions interact with anthropogenic warming unforeseen multiplier effects may occur.

Does tallgrass prairie restoration enhance the invasion resistance of post-agricultural lands? - Bryan L. Foster; Gregory R. Houseman; David R. Hall; Sarah E. Hinman (Biological Invasions, 2015)

Pollen–climate reconstruction from northern South Island, New Zealand (41°S), reveals varying high‐ and low‐latitude teleconnections over the last 16 000 years - Ignacio A. Jara; Rewi M. Newnham; Marcus J. Vandergoes; Courtney R. Foster; David J. Lowe; Janet M. Wilmshurst; Patricio I. Moreno; James A. Renwick; Aline M. Homes (Journal of Quaternary Science, 2015)
We present a 16 000‐year vegetation and climate reconstruction from pollen and plant macrofossil records obtained at a small alpine lake in South Island, New Zealand (41°S). The expansion of lowland forest taxa suggests a lifting of the altitudinal forest limits because of a warming pulse between 13 and 10k cal a BP and between 7 and 6k cal a BP, while their decline relative to upland forest taxa indicates cooling phases between 10 and 7k cal a BP and over the last 3000 years. The modern treeline was first established locally by 9.7k cal a BP. Forest persisted at the site until 3k cal a BP then disappeared from the record. Close correspondence between the temperature trends inferred from the pollen and macrofossil records and proxies from Antarctica and the Southern Ocean suggests a strong teleconnection between New Zealand and the Southern Hemisphere high‐latitudes between 15 and 6k cal a BP. We note that the breakdown of this coupling, a cooling trend in Adelaide Tarn and the local disappearance of beech forest after 3k cal a BP occur during a period of increased frequency of El Niño events, suggesting an enhanced teleconnection with the low‐latitudes during the late Holocene.

An ant–plant by-product mutualism is robust to selective logging of rain forest and conversion to oil palm plantation - Tom M. Fayle; David P. Edwards; William A. Foster; Kalsum M. Yusah; Edgar C. Turner (Oecologia, 2015)

Climate remains an important driver of post‐European vegetation change in the eastern United States - Neil Pederson; Anthony W. D'Amato; James M. Dyer; David R. Foster; David Goldblum; Justin L. Hart; Amy E. Hessl; Louis R. Iverson; Stephen T. Jackson; Dario Martin‐Benito; Brian C. McCarthy; Ryan W. McEwan; et al. (Global Change Biology, 2015)

Model-based thinking for community ecology - David I. Warton; Scott D. Foster; Glenn De’ath; Jakub Stoklosa; Piers K. Dunstan (Plant Ecology, 2015)

Characterization of ANKRD11 mutations in humans and mice related to KBG syndrome - Katherina Walz; Devon Cohen; Paul M. Neilsen; Joseph Foster; Francesco Brancati; Korcan Demir; Richard Fisher; Michelle Moffat; Nienke E. Verbeek; Kathrine Bjørgo; Adriana Lo Castro; Paolo Curatolo; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Delineating optimal settlement areas of juvenile reef fish in Ngederrak Reef, Koror state, Republic of Palau - Victor S. Ticzon; Greg Foster; Laura T. David; Peter J. Mumby; Badi R. Samaniego; Val Randolf Madrid (Environmental Monitoring and Assessment, 2015)

Evidence of land‐sea transfer of the zoonotic pathogen Campylobacter to a wildlife marine sentinel species - Johanna L. Baily; Guillaume Méric; Sion Bayliss; Geoffrey Foster; Simon E. Moss; Eleanor Watson; Ben Pascoe; Jane Mikhail; Romain Pizzi; Robert J. Goldstone; David G. E. Smith; Kim Willoughby; et al. (Molecular Ecology, 2015)
Environmental pollution often accompanies the expansion and urbanization of human populations where sewage and wastewaters commonly have an impact on the marine environments. Here, we explored the potential for faecal bacterial pathogens, of anthropic origin, to spread to marine wildlife in coastal areas. The common zoonotic bacterium Campylobacter was isolated from grey seals ( Halichoerus grypus ), an important sentinel species for environmental pollution, and compared to isolates from wild birds, agricultural sources and clinical samples to characterize possible transmission routes. Campylobacter jejuni was present in half of all grey seal pups sampled (24/50 dead and 46/90 live pups) in the breeding colony on the Isle of May (Scotland), where it was frequently associated with histological evidence of disease. Returning yearling animals (19/19) were negative for C . jejuni suggesting clearance of infection while away from the localized colony infection source. The genomes of 90 isolates from seals were sequenced and characterized using a whole‐genome multilocus sequence typing ( MLST ) approach and compared to 192 published genomes from multiple sources using population genetic approaches and a probabilistic genetic attribution model to infer the source of infection from MLST data. The strong genotype‐host association has enabled the application of source attribution models in epidemiological studies of human campylobacteriosis, and here assignment analyses consistently grouped seal isolates with those from human clinical samples. These findings are consistent with either a common infection source or direct transmission of human campylobacter to grey seals, raising concerns about the spread of human pathogens to wildlife marine sentinel species in coastal areas.

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Selection of low-variance expressed Malus x domestica (apple) genes for use as quantitative PCR reference genes (housekeepers) - Judith Bowen; Hilary S. Ireland; Ross Crowhurst; Zhiwei Luo; Amy E. Watson; Toshi Foster; Nigel Gapper; Jim J. Giovanonni; James P. Mattheis; Chris Watkins; David Rudell; Jason W. Johnston; et al. (Tree Genetics & Genomes, 2014)

Development of anonymous nuclear markers from Illumina paired-end data for Seychelles caecilian amphibians (Gymnophiona: Indotyphlidae) - Claire J. Lewis; Simon T. Maddock; Julia J. Day; Ronald A. Nussbaum; Charles Morel; Mark Wilkinson; Peter G. Foster; David J. Gower (Conservation Genetics Resources, 2014)
Anonymous nuclear markers were developed for Seychelles caecilian amphibians. Using a previously published bioinformatics pipeline (developed for Roche 454 data), 36 candidate anonymous nuclear loci (ANL) of at least 180 bp length were identified from Illumina MiSeq next generation sequencing data for five Seychelles species. We designed primer pairs for the 36 candidate ANL and tested these by PCR and Sanger sequencing. Seven ANL amplified and sequenced well for at least five of the six nominal Seychelles caecilian species (in three genera), and represent potentially useful markers for systematics and conservation.

Extensional deformation along the southern boundary of the Gyeonggi Massif, South Korea: structural characteristics, age constraints, and tectonic implications - Raehee Han; Kyoungwon Min; Jin-Han Ree; David A. Foster (International Journal of Earth Sciences, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

To mix or not to mix: comparing the predictive performance of mixture models vs. separate species distribution models - Francis K. C. Hui; David I. Warton; Scott D. Foster; Piers K. Dunstan (Ecology, 2013)
Species distribution models (SDMs) are an important tool for studying the patterns of species across environmental and geographic space. For community data, a common approach involves fitting an SDM to each species separately, although the large number of models makes interpretation difficult and fails to exploit any similarities between individual species responses. A recently proposed alternative that can potentially overcome these difficulties is species archetype models (SAMs), a model‐based approach that clusters species based on their environmental response. In this paper, we compare the predictive performance of SAMs against separate SDMs using a number of multi‐species data sets. Results show that SAMs improve model accuracy and discriminatory capacity compared to separate SDMs. This is achieved by borrowing strength from common species having higher information content. Moreover, the improvement increases as the species become rarer.

Rheological control on the tectonic evolution of a continental suture zone: the Variscan example from NW Iberia (Spain) - Rubén Díez Fernández; David A. Foster; Juan Gómez Barreiro; Montserrat Alonso-García (International Journal of Earth Sciences, 2013)

Exercise-induced endocannabinoid signaling is modulated by intensity - David A. Raichlen; Adam D. Foster; Alexandre Seillier; Andrea Giuffrida; Gregory L. Gerdeman (European Journal of Applied Physiology, 2013)

Erratum to: A physiologically-based recirculatory meta-model for nasal fentanyl in man - Richard N. Upton; David J. R. Foster; Lona L. Christrup; Ola Dale; Kristin Moksnes; Lars Popper (Journal of Pharmacokinetics and Pharmacodynamics, 2013)

Survivors, not invaders, control forest development following simulated hurricane - Audrey Barker Plotkin; David Foster; Joel Carlson; Alison Magill (Ecology, 2013)
Wind disturbance profoundly shapes temperate forests but few studies have evaluated patterns and mechanisms of long‐term forest dynamics following major windthrows. In 1990, we initiated a large hurricane simulation experiment in a 0.8‐ha manipulation (pulldown) and 0.6‐ha control area of a maturing Quercus rubra – Acer rubrum forest in New England. We toppled 276 trees in the pulldown, using a winch and cable, in the northwesterly direction of natural treefall from major hurricanes. Eighty percent of canopy trees and two‐thirds of all trees ≥5 cm dbh (diameter at breast height) suffered direct and indirect damage. We used 20 years of measurements to evaluate the trajectory and mechanisms of forest response after intense disturbance. Based on the patch size and disturbance magnitude, we expected pioneer tree and understory species to drive succession. The first decade of analyses emphasized tree seedling establishment and sprouting by damaged trees as the dominant mechanisms of forest recovery in this extensive damaged area. However, despite 80% canopy damage and 8000‐m 2 patch size, surviving overstory and advance regeneration controlled longer‐term forest development. Residual oaks make up 42% of stand basal area after 20 years. The new cohort of trees, dominated by black birch advance regeneration, contributes 30% of stand basal area. There were shifts in understory vegetation composition and cover, but few species were gained or lost after 20 years. Stand productivity rebounded quickly (litterfall recovered to pre‐disturbance levels in six years), but we predict that basal area in the pulldown will lag behind the control (which gained 6 m 2 /ha over 20 years) for decades to come. This controlled experiment showed that although the scale and intensity of damage were great, abundant advance regeneration, understory vegetation, and damaged trees remained, allowing the forest to resist changes in ecosystem processes and invasion by new species.

Contrasting effects of sunitinib within in vivo models of metastasis - Jonathan C. Welti; Thomas Powles; Shane Foo; Morgane Gourlaouen; Natasha Preece; Julie Foster; Sophia Frentzas; Demelza Bird; Kevin Sharpe; Antoinette van Weverwijk; David Robertson; Julie Soffe; et al. (Angiogenesis, 2012)

A physiologically-based recirculatory meta-model for nasal fentanyl in man - Richard N. Upton; David J. R. Foster; Lona L. Christrup; Ola Dale; Kristin Moksnes; Lars Popper (Journal of Pharmacokinetics and Pharmacodynamics, 2012)

Glaciotectonic deformation associated with the Orient Point–Fishers Island moraine, westernmost Block Island Sound: further evidence of readvance of the Laurentide ice sheet - Lawrence J. Poppe; Robert N. Oldale; David S. Foster; Shepard M. Smith (Geo-Marine Letters, 2012)

An integrated reconstruction of recent forest dynamics in a New England cultural landscape - Alex W. Ireland; W. Wyatt Oswald; David R. Foster (Vegetation History and Archaeobotany, 2011)

CYP2C19-guided design of a proton pump inhibitor dose regimen to avoid the need for pharmacogenetic individualisation in H. pylori eradication - Michael B. Ward; David J. R. Foster (European Journal of Clinical Pharmacology, 2011)

The synthetic triterpenoid CDDO-Imidazolide suppresses experimental liver metastasis - Jason L. Townson; Ian C. MacDonald; Karen T. Liby; Lisa Mackenzie; David W. Dales; Benjamin D. Hedley; Paula J. Foster; Michael B. Sporn; Ann F. Chambers (Clinical & Experimental Metastasis, 2011)

Prediction of Human Metabolic Clearance from In Vitro Systems: Retrospective Analysis and Prospective View - David Hallifax; Joanne A. Foster; J. Brian Houston (Pharmaceutical Research, 2010)

Hepatocellular hypertrophy and cell proliferation in Sprague–Dawley rats following dietary exposure to ammonium perfluorooctanoate occurs through increased activation of the xenosensor nuclear receptors PPARα and CAR/PXR - Clifford R. Elcombe; Barbara M. Elcombe; John R. Foster; David G. Farrar; Reinhard Jung; Shu-Ching Chang; Gerald L. Kennedy; John L. Butenhoff (Archives of Toxicology, 2010)

A record of Holocene environmental and ecological changes from Wildwood Lake, Long Island, New York - W. Wyatt Oswald; David R. Foster; Elaine D. Doughty; Dana Macdonald (Journal of Quaternary Science, 2010)
Analyses of pollen, charcoal and organic content in a lake sediment core from Wildwood Lake, Long Island, New York, provide insights into the ecological and environmental history of this region. The early Holocene interval of the record (ca. 9800–8800 cal. a BP) indicates the presence of Pinus rigida – Quercus ilicifolia woodlands with high fire activity. A layer of sandy sediment dating to 9200 cal. a BP may reflect a brief period of reduced water depth, consistent with widespread evidence for cold, dry conditions at that time. Two other sandy layers, bracketed by 14 C dates, represent a sedimentary hiatus from ca. 8800 to 4500 cal. a BP. This discontinuity may reflect the removal of some sediment during brief periods of reduced water depth at 5300 and 4600 cal. a BP. In the upper portion of the record ( Quercus – Fagus – Carya forests and increasing abundance of Pinus rigida , perhaps due to reduced summer precipitation. Elevated percentages of herbaceous taxa in the uppermost sediments represent European agricultural activities. However, unlike charcoal records from southern New England, fire activity does not increase dramatically with European settlement. These findings indicate that present‐day Pinus rigida – Quercus ilicifolia woodlands on eastern Long Island are not a legacy of recent, anthropogenic disturbances. Copyright © 2010 John Wiley & Sons, Ltd.

A record of Lateglacial and early Holocene environmental and ecological change from southwestern Connecticut, USA - W. Wyatt Oswald; David R. Foster; Elaine D. Doughty; Edward K. Faison (Journal of Quaternary Science, 2009)
Analyses of a sediment core from Highstead Swamp in southwestern Connecticut, USA, reveal Lateglacial and early Holocene ecological and hydrological changes. Lateglacial pollen assemblages are dominated by Picea and Pinus subg. Pinus , and the onset of the Younger Dryas (YD) cold interval is evidenced by higher abundance of Abies and Alnus viridis subsp. crispa . As climate warmed at the end of the YD, Picea and Abies declined and Pinus strobus became the dominant upland tree species. A shift from lacustrine sediment to organic peat at the YD–Holocene boundary suggests that the lake that existed in the basin during the Lateglacial interval developed into a swamp in response to reduced effective moisture. A change in wetland vegetation from Myrica gale to Alnus incana subsp. rugosa and Sphagnum is consistent with this interpretation of environmental changes at the beginning of the Holocene. Copyright © 2009 John Wiley & Sons, Ltd.

PanTHERIA: a species‐level database of life history, ecology, and geography of extant and recently extinct mammals - Kate E. Jones; Jon Bielby; Marcel Cardillo; Susanne A. Fritz; Justin O'Dell; C. David L. Orme; Kamran Safi; Wes Sechrest; Elizabeth H. Boakes; Chris Carbone; Christina Connolly; Michael J. Cutts; et al. (Ecology, 2009)
Analyses of life‐history, ecological, and geographic trait differences among species, their causes, correlates, and likely consequences are increasingly important for understanding and conserving biodiversity in the face of rapid global change. Assembling multispecies trait data from diverse literature sources into a single comprehensive data set requires detailed consideration of methods to reliably compile data for particular species, and to derive single estimates from multiple sources based on different techniques and definitions. Here we describe PanTHERIA, a species‐level data set compiled for analysis of life history, ecology, and geography of all known extant and recently extinct mammals. PanTHERIA is derived from a database capable of holding multiple geo‐referenced values for variables within a species containing 100 740 lines of biological data for extant and recently extinct mammalian species, collected over a period of three years by 20 individuals. PanTHERIA also includes spatial databases of mammalian geographic ranges and global climatic and anthropogenic variables. Here we detail how the data fields are extracted and defined for PanTHERIA using a customized data input format (MammalForm); how data were collected from the literature, species names and sources tracked, error‐checking and validation procedures applied, and how data were consolidated into species‐level values for each variable. Tables of the consolidated species‐level values are made available for each of two recent species‐level taxonomic classifications of mammals, as well as associated taxonomic synonymy conversion and data‐input files. This study provides a useful guide to prospective researchers on how to structure and codify life‐history, ecological, geographic, and taxonomic data and methods to extract meaningful species‐level traits. It also provides comprehensive information on traits like size, diet, environmental conditions, and ecology to permit macroecological and macroevolutionary analyses of this important clade. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

Lyophilization of Spodoptera frugiperda (Lepidoptera: Noctuidae) larvae yields high-quality DNA for use in AFLP genetic studies - Pete L. Clark; David J. Isenhour; Steven R. Skoda; Jaime Molina-Ochoa; Claudia Gianni; John E. Foster (International Journal of Tropical Insect Science, 2009)

Population based models of cortical drug response: insights from anaesthesia - Brett L. Foster; Ingo Bojak; David T. J. Liley (Cognitive Neurodynamics, 2008)

Estimating the Effect of Protected Lands on the Development and Conservation of Their Surroundings - ROBERT I. McDONALD; CHRIS YUAN‐FARRELL; CHARLES FIEVET; MATTHIAS MOELLER; PETER KAREIVA; DAVID FOSTER; TED GRAGSON; ANN KINZIG; LAUREN KUBY; CHARLES REDMAN (Conservation Biology, 2007)
The fate of private lands is widely seen as key to the fate of biodiversity in much of the world. Organizations that work to protect biodiversity on private lands often hope that conservation actions on one piece of land will leverage the actions of surrounding landowners. Few researchers have, however, examined whether protected lands do in fact encourage land conservation nearby or how protected lands affect development in the surrounding landscape. Using spatiotemporal data sets on land cover and land protection for three sites (western North Carolina, central Massachusetts, and central Arizona), we examined whether the existence of a protected area correlates with an increased rate of nearby land conservation or a decreased rate of nearby land development. At all sites, newly protected conservation areas tended to cluster close to preexisting protected areas. This may imply that the geography of contemporary conservation actions is influenced by past decisions on land protection, often made for reasons far removed from concerns about biodiversity. On the other hand, we found no evidence that proximity to protected areas correlates with a reduced rate of nearby land development. Indeed, on two of our three sites the development rate was significantly greater in regions with more protected land. This suggests that each conservation action should be justified and valued largely for what is protected on the targeted land, without much hope of broader conservation leverage effects.

Population pharmacokinetics of buprenorphine following a two-stage intravenous infusion in healthy volunteers - Mette L. Jensen; David J. R. Foster; Richard N. Upton; Kim Kristensen; Steen H. Hansen; Niels-Henrik Jensen; Bettina N. Nielsen; Ulrik Skram; Hanne H. Villesen; Lona Christrup (European Journal of Clinical Pharmacology, 2007)

Genetic structure and evolved malaria resistance in Hawaiian honeycreepers - JEFFREY T. FOSTER; BETHANY L. WOODWORTH; LORI E. EGGERT; PATRICK J. HART; DANIELLE PALMER; DAVID C. DUFFY; ROBERT C. FLEISCHER (Molecular Ecology, 2007)
Infectious diseases now threaten wildlife populations worldwide but population recovery following local extinction has rarely been observed. In such a case, do resistant individuals recolonize from a central remnant population, or do they spread from small, perhaps overlooked, populations of resistant individuals? Introduced avian malaria ( Plasmodium relictum ) has devastated low‐elevation populations of native birds in Hawaii, but at least one species (Hawaii amakihi, Hemignathus virens ) that was greatly reduced at elevations below about 1000 m tolerates malaria and has initiated a remarkable and rapid recovery. We assessed mitochondrial and nuclear DNA markers from amakihi and two other Hawaiian honeycreepers, apapane ( Himatione sanguinea ) and iiwi ( Vestiaria coccinea ), at nine primary study sites from 2001 to 2003 to determine the source of re‐establishing birds. In addition, we obtained sequences from tissue from amakihi museum study skins (1898 and 1948–49) to assess temporal changes in allele distributions. We found that amakihi in lowland areas are, and have historically been, differentiated from birds at high elevations and had unique alleles retained through time; that is, their genetic signature was not a subset of the genetic variation at higher elevations. We suggest that high disease pressure rapidly selected for resistance to malaria at low elevation, leaving small pockets of resistant birds, and this resistance spread outward from the scattered remnant populations. Low‐elevation amakihi are currently isolated from higher elevations (> 1000 m) where disease emergence and transmission rates appear to vary seasonally and annually. In contrast to results from amakihi, no genetic differentiation between elevations was found in apapane and iiwi, indicating that slight variation in genetic or life‐history attributes can determine disease resistance and population recovery. Determining the conditions that allow for the development of resistance to disease is essential to understanding how species evolve resistance across a landscape of varying disease pressures.

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

Preemptive and Salvage Harvesting of New England Forests: When Doing Nothing Is a Viable Alternative - DAVID R. FOSTER; DAVID A. ORWIG (Conservation Biology, 2006)
One unexpected consequence of natural disturbances in forested areas is that managers often initiate activities that may impose greater ecosystem impacts than the disturbances themselves. By salvage logging areas affected by windstorms or other impacts, by harvesting host trees in advance of insect infestation or disease, or by preemptively harvesting forests in an attempt to improve their resilience to future disturbances and stresses, managers initiate substantial changes in the ecosystem structure and function. Much of this activity is undertaken in the absence of information on the qualitative and quantitative differences between disturbance impacts and harvesting. To provide insight for such decisions we evaluated the ecosystem consequences of two major disturbance processes in New England (U.S.A.)—intense windstorms and invasive pests and pathogens—and contrasted them with impacts from preemptive and salvage harvesting. Despite dramatic physical changes in forest structure resulting from hurricane impacts and insect infestation, little disruption of biogeochemical processes or other ecosystem functions typically follows these disturbances. Indeed, the physical and organic structures produced by these disturbances are important natural features providing habitat and landscape heterogeneity that are often missing due to centuries of land use. From an ecosystem perspective there are strong arguments against preemptive and salvage logging or the attempt through silvicultural means to improve the resistance or resilience of forests to disturbance and stress. There are often valid motivations for salvage or preemptive logging including financial considerations, human safety, and a desire to shape the long‐term composition and resource‐production characteristics of forests. Nonetheless, there are many ecological benefits derived from leaving forests alone when they are affected or threatened by disturbances and pest and pathogen outbreaks.

The GeoProfile metadata, exposure of instruments, and measurement bias in climatic record revisited - Rezaul Mahmood; Stuart A. Foster; David Logan (International Journal of Climatology, 2006)

Testing metabolic ecology theory for allometric scaling of tree size, growth and mortality in tropical forests - Helene C. Muller‐Landau; Richard S. Condit; Jerome Chave; Sean C. Thomas; Stephanie A. Bohlman; Sarayudh Bunyavejchewin; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; Kyle E. Harms; Terese Hart; et al. (Ecology Letters, 2006)
The theory of metabolic ecology predicts specific relationships among tree stem diameter, biomass, height, growth and mortality. As demographic rates are important to estimates of carbon fluxes in forests, this theory might offer important insights into the global carbon budget, and deserves careful assessment. We assembled data from 10 old‐growth tropical forests encompassing censuses of 367 ha and > 1.7 million trees to test the theory's predictions. We also developed a set of alternative predictions that retained some assumptions of metabolic ecology while also considering how availability of a key limiting resource, light, changes with tree size. Our results show that there are no universal scaling relationships of growth or mortality with size among trees in tropical forests. Observed patterns were consistent with our alternative model in the one site where we had the data necessary to evaluate it, and were inconsistent with the predictions of metabolic ecology in all forests.

Comparing tropical forest tree size distributions with the predictions of metabolic ecology and equilibrium models - Helene C. Muller‐Landau; Richard S. Condit; Kyle E. Harms; Christian O. Marks; Sean C. Thomas; Sarayudh Bunyavejchewin; George Chuyong; Leonardo Co; Stuart Davies; Robin Foster; Savitri Gunatilleke; Nimal Gunatilleke; et al. (Ecology Letters, 2006)
Tropical forests vary substantially in the densities of trees of different sizes and thus in above‐ground biomass and carbon stores. However, these tree size distributions show fundamental similarities suggestive of underlying general principles. The theory of metabolic ecology predicts that tree abundances will scale as the −2 power of diameter. Demographic equilibrium theory explains tree abundances in terms of the scaling of growth and mortality. We use demographic equilibrium theory to derive analytic predictions for tree size distributions corresponding to different growth and mortality functions. We test both sets of predictions using data from 14 large‐scale tropical forest plots encompassing censuses of 473 ha and > 2 million trees. The data are uniformly inconsistent with the predictions of metabolic ecology. In most forests, size distributions are much closer to the predictions of demographic equilibrium, and thus, intersite variation in size distributions is explained partly by intersite variation in growth and mortality.

The Acute Disposition of (R)- and (S)-Methadone in Brain and Lung of Sheep - David J. R. Foster; Richard N. Upton; Andrew A. Somogyi; Cliff Grant; Allison Martinez (Journal of Pharmacokinetics and Pharmacodynamics, 2005)

Timing of orogenic gold mineralisation in northeastern Tasmania: implications for the tectonic and metallogenetic evolution of Palaeozoic SE Australia - Frank P. Bierlein; David A. Foster; David R. Gray; Garry J. Davidson (Mineralium Deposita, 2005)

Influence of Targets and Assessment Region Size on Perceived Conservation Priorities - David D. Diamond; C. Diane True; Taisia M. Gordon; Scott P. Sowa; Walter E. Foster; K. Bruce Jones (Environmental Management, 2005)

Comparing the effects of farming practices on ground beetle (Coleoptera: Carabidae) and spider (Araneae) assemblages of Scottish farmland - Lorna J. Cole; David I. McCracken; Iain S. Downie; Peter Dennis; Garth N. Foster; Tony Waterhouse; Kevin J. Murphy; Anna L. Griffin; Mike P. Kennedy (Biodiversity and Conservation, 2005)

A critical analysis of reasons for improved survival from invasive cutaneous melanoma - Colin Glen Luke; Brendon John Coventry; Erwin Joseph Foster-Smith; David Murray Roder (Cancer Causes & Control, 2003)

Tachykinin substance P signaling involved in diesel exhaust-induced bronchopulmonary neurogenic inflammation in rats - Simon S. Wong; Nina N. Sun; Ingegerd Keith; Chol-Bum Kweon; David E. Foster; James J. Schauer; Mark L. Witten (Archives of Toxicology, 2003)

Comparison of Human Duodenum and Caco-2 Gene Expression Profiles for 12,000 Gene Sequences Tags and Correlation with Permeability of 26 Drugs - Duxin Sun; Hans Lennernas; Lynda S. Welage; Jeffery L. Barnett; Christopher P. Landowski; David Foster; David Fleisher; Kyung-Dall Lee; Gordon L. Amidon (Pharmaceutical Research, 2002)

Vegetation variation across Cape Cod, Massachusetts: environmental and historical determinants - Glenn Motzkin; Robert Eberhardt; Brian Hall; David R. Foster; Jonathan Harrod; Dana MacDonald (Journal of Biogeography, 2002)
Aim We evaluate environmental and historical determinants of modern species composition for upland vegetation types across Cape Cod, Massachusetts, a region that supports numerous uncommon species assemblages that are conservation priorities. Location The study area encompasses the entire peninsula of Cape Cod, Massachusetts, USA. Methods Historical changes in land‐use and land‐cover across the study region were determined from historical maps and documentary sources. Modern vegetation and soils were sampled and land‐use and fire history determined for 352 stratified‐random study plots. Ordination and classification were used to assess vegetation variation, and G ‐tests of independence and Kruskal–Wallis tests were used to evaluate relationships among individual species distributions, past land‐use, surficial landforms and edaphic conditions. Results At the scale of this investigation, modern species distributions result from individualistic response to a range of environmental and historical factors, including geography, substrate and disturbance history, especially the pattern of past agricultural activity. The structure or composition of all vegetation types in the region have been shaped by past land‐use, fire, or other disturbances, and vegetation patterns will continue to change through time. Conservation efforts aimed at maintaining early successional vegetation types may require intensive management comparable in intensity to the historical disturbances that allowed for their widespread development.

Three hundred years of forest and land‐use change in Massachusetts, USA - Brian Hall; Glenn Motzkin; David R. Foster; Mindy Syfert; John Burk (Journal of Biogeography, 2002)
Aim The aim of this study was to document changes in forest composition, structure and distribution across Massachusetts, USA, from the time of European settlement (seventeenth century) to the present, and to investigate environmental and historical influences on regional patterns of variation. Location The study area encompasses the State of Massachusetts (69.9–73.5°E, 41.3–42.9°N), a 21,000‐km 2 area in the north‐eastern United States. Methods A wide range of historical sources was used to document changes in land use and land cover for the historical period. Witness trees from early land surveys enabled us to evaluate vegetation patterns prior to widespread European settlement, and to compare historical and modern species composition. Nineteenth century maps of forest cover and contemporary agricultural censuses documented forest patterns during the peak agricultural period. Geographic Information System analyses were used to relate variation in climate, geology and land‐use history to historical and modern forest composition. Results Massachusetts has a complex east‐to‐west environmental gradient involving changes in physiography, climate, geology and natural disturbance. Until the middle of the twentieth century, agriculture was the most important land‐use across the region; although the percentage of land in agriculture and the timing of major land‐use changes were remarkably consistent across the state, historical forest patch sizes varied locally and regionally in relation to physiography. Forest composition of both early historical and modern forests is most strongly related to environmental conditions, especially variation in climate. Historical land‐use resulted in a state‐wide increase in early successional tree species and a dramatic, although recovering, change in forest structure. Main conclusions At a regional scale, environmental conditions apparently control broad patterns of variation in vegetation composition. Historical land‐use practices were relatively homogenous across Massachusetts and local variation was reduced through data averaging at broad spatial scales. At finer spatial scales, historical land‐use has strong and persistent impacts on vegetation composition and structure.

Landscape patterns of hemlock decline in New England due to the introduced hemlock woolly adelgid - David A. Orwig; David R. Foster; David L. Mausel (Journal of Biogeography, 2002)
Aim The hemlock woolly adelgid (HWA; Adelges tsugae Annand), a small, aphid‐like insect native to Japan, is currently migrating northward through eastern North America and threatens to eliminate eastern hemlock [ Tsuga canadensis (L.) Carriere], one of the most abundant, long‐lived shade tolerant species, across its range. The major objectives of this study were: (1) to characterize the pre‐HWA distribution, composition, and structure of hemlock stands; (2) to characterize the spatial patterns of damage generated by HWA across southern New England since the time of its arrival in 1985; and (3) to examine environmental and stand factors that are associated with declines in crown vigour and mortality of hemlock. Location Our study was conducted in a 4900‐km 2 study region extending from Long Island Sound northward to the Massachusetts border and including the Connecticut River Valley in Connecticut, USA. Methods Aerial photographs and extensive field study were used to map and develop GIS overlays of 1000 hemlock stands in our study region. Intensive sampling of a random selection of 114 hemlock stands across the study area was used to document patterns of hemlock infestation, vigour, and mortality in relation to stand and site characteristics. Mantel tests were utilized to assess the relative importance of environmental and stand variables in controlling the intensity of HWA infestation and damage. Results Most stands were located along ridge tops, steep hillsides and narrow valleys. Hemlock importance values ranged from 22 to 96% and stand densities varied from 300 to 1450 stems ha – 1 . Adelgid presence and adelgid‐induced hemlock mortality were found in 88 and 74% of the sampled forests, respectively. Approximately 25% of stands were logged recently, ranging in intensity from partial hemlock cutting to large clearcuts. A geographical trend in reduced HWA infestation intensity and tree mortality and enhanced crown vigour of overstory and understory hemlock occurs from south to north, coincident with the temporal colonization pattern of HWA. Mantel analyses indicated that patterns of HWA infestation, hemlock mortality, and crown vigour were most strongly correlated with latitude. Mortality was also weakly related to aspect and stand size. Average mortality was highest on western aspects but exceeded 20% on most slopes. Remaining trees averaged over 50% foliar loss, with no significant difference among aspects. Main conclusions Results suggest that as HWA becomes abundant, stands on xeric aspects succumb rapidly, but that stand and landscape variables such as overstory composition and structure, slope, and elevation, exert little control over susceptibility or eventual mortality. Ultimately, duration of infestation controls the intensity of hemlock decline and mortality. Over 4290 ha of hemlock forest have been eliminated by logging or HWA just within the southern part of our transect since the mid‐1980s, and we predict continued HWA infestation will lead to unprecedented hemlock loss throughout the north‐eastern USA, regardless of site conditions or location.

Direct and indirect ecosystem consequences of an invasive pest on forests dominated by eastern hemlock - Matthew L. Kizlinski; David A. Orwig; Richard C. Cobb; David R. Foster (Journal of Biogeography, 2002)
Aim This study compares the magnitude and trajectory of vegetation and ecosystem function dynamics associated with the direct impact of hemlock woolly adelgid ( Adelges tsugae Annand; HWA) infestation vs. the indirect consequences of HWA‐induced damage in the form of salvage and pre‐emptive logging of hemlock [ Tsuga canadensis (L.) Carriere] forests. Location The study was conducted within an area extending from southern Connecticut up to and including the Connecticut River lowlands west to the Berkshire Plateau in central Massaschusetts, USA. Methods Overstorey and understorey vegetation and ecosystem function parameters such as decomposition and nitrogen cycling were examined in logged and unlogged portions of ten hemlock stands varying in HWA damage intensity. Results Intensive hemlock logging generated more rapid and pronounced microenvironment and vegetation changes than chronic HWA damage. Black birch ( Betula lenta L.) seedling densities and percent cover of brambles ( Rubus L. spp.), sedges ( Carex L. spp.) and hay‐scented fern ( Dennstaedtia punctilobula Michx.) were significantly higher in recent harvests vs. HWA‐damaged and undamaged sites. High black birch sapling densities (>7000 ha −1 ) were common in the older harvests but not in adjacent, HWA‐damaged portions of these sites. Undamaged sites had 20% more forest floor mass than HWA‐damaged sites and double the mass of older cuts. Mass loss rates of cellulose paper suggest that conditions were more favourable for decomposition in the damaged and older logged sites. Recently cut sites had significantly larger inorganic N pools than undamaged forests, although total net nitrogen (N) mineralization rates were not significantly different among treatments. Nitrification rates of 0.2 kg ha −1 day −1 measured in the oldest cuts were three times greater than in HWA‐damaged sites and over 200 times greater than in undamaged hemlock sites. However, resin bag capture in the older cuts was similar to amounts captured in undamaged and damaged forests, suggesting that excess nitrogen was being utilized in vegetative uptake. In contrast, relatively large amounts of ammonium and nitrate captured in recent harvests indicate higher N availability, less vegetative uptake, and a greater potential for N leaching. Main conclusions Results suggest that both the decline associated with HWA infestation and the indirect effects of HWA in the form of logging are generating profound changes in structure, composition, and ecosystem function in these forests, although at different spatial and temporal scales. Hemlock harvesting imposed more abrupt microenvironmental changes, and rapidly reduced vegetative cover while chronic HWA infestation led to gradually thinning canopies. Both disturbances led to black birch dominated forests, although logging resulted in greater amounts of shade‐intolerant regeneration, higher soil pH and nitrification rates, and reduced forest floor mass. Pre‐emptive cutting of undamaged forests may lead to greater N losses than those associated with HWA infestation or logging of deteriorated hemlock forests, because of reduced vegetative uptake. Silvicultural methods that allow for vegetation establishment prior to harvesting will probably lessen the ecological impacts of hemlock removal.

Physiographical and historical effects on forest vegetation in central New England, USA - Fritz Gerhardt; David R. Foster (Journal of Biogeography, 2002)
Aim Land‐use history can be an important determinant of ecosystem characteristics, even in landscapes that outwardly appear ‘natural’. In New England, like much of the eastern United States, the natural reforestation of agricultural lands over the past 150 years has created a predominantly forested landscape. Understanding the physiographical and historical factors controlling forest structure and composition is a major challenge to ecologists, conservationists and land managers. Location We studied the forest structure and composition of Petersham, Massachusetts, which is located in the Central Upland physiographical province of New England. Like much of New England, Petersham was largely cleared for agriculture by the mid‐1800s, but most of the agricultural fields were abandoned and naturally reforested in the late‐1800s and early 1900s. The modern landscape is > 90% forested by a mosaic of primary and secondary woodlands. Methods At seventy‐four randomly selected 0.04‐ha plots, we measured the abundances of all vascular plants in the overstory and understory and nine physiographical and historical variables. Results Species richness was primarily related to landform: species‐rich communities occurred in poorly drained basins and species‐poor communities occurred on well‐drained glacial outwash. Distributions of the sixty‐nine most common species were associated with (in order of importance) landform, past land use and elevation. Many species were restricted to specific physiographical conditions, but no species were restricted to specific past land uses. Nine plant associations identified by two‐way indicator species analysis were associated with elevation, landform, soil texture and past land use. Ordination by canonical correspondence analysis indicated that the vegetation reflected two principal gradients: a physiographical gradient, defined by landform and soil texture, and a land‐use gradient. Main conclusions These analyses suggest the following ranking of factors controlling forest structure and composition in this landscape at this time: landform > agricultural history > elevation > hurricane = fire = logging. Even in this physically heterogenous landscape, land‐use history continues to play an important role in shaping forest vegetation 100–150 years after agricultural abandonment and reforestation.

Wildlife dynamics in the changing New England landscape - David R. Foster; Glenn Motzkin; Debra Bernardos; James Cardoza (Journal of Biogeography, 2002)
Aim Over the past four centuries the eastern US has undergone remarkable landscape and land‐use transformations involving deforestation, intensive agriculture, farm abandonment, reforestation and human population increase that have induced sweeping changes in wildlife assemblages, abundances, and distributions. This study compiles data on major wildlife species and seeks to identify broad population trends and to address both fundamental and applied questions regarding these long‐term patterns. Location The study encompasses the state of Massachusetts, which is broadly representative of the habitat conditions and landscape and cultural history of other New England states. Methods A wide range of historical sources of data were used including town histories, newspaper and other popular accounts, scientific studies, museum collections, compiled trapping, bounty and harvest records, explorer accounts, and agency records. Statewide distribution maps and generalized population trends were assembled for individual species where practical, and major trends in species trajectories were identified. Emphasis was placed on mammals and birds for which data are readily available. Results Although species exhibited highly individualistic long‐term dynamics in response to habitat change and human pressure, six major trajectories of species changes are identified: (1) large mammals and birds that declined historically and increased recently, (2) open‐land species that went from low to high abundance with the creation of open habitat but are in rapid decline today in the heavily wooded landscape, (3) species regionally extirpated or globally extinct, (4) species expanding their range from the west, north and south, (5) non‐native, introduced species, and (6) persistent species not exhibiting major long‐term trends. Currently, wildlife populations are changing at a remarkable rate leading to significant ecological impacts on the landscape and many other species, creating major conservation and management challenges, and generating novel and oftentimes significant conflicts with human values. Conclusions The rate of historical and current changes in wildlife assemblages pose many scientific and conservation challenges, especially in this heavily forested but highly populated landscape. Historical data are fragmentary and oftentimes uncertain, modern information on wildlife populations is similarly incomplete, and small populations of species that are immigrating, expanding or declining from previously high levels pose major sampling problems; development of conservation and management plans for rapidly expanding populations of large woodland mammals (e.g. moose, coyote, deer, bears, beaver) and for declining populations of cherished species that are dependent on cultural landscapes generates conflicting directives; and educating, and modifying the behaviour of a human population that is living in but separated from nature is a difficult enterprise. The future is guaranteed to bring major dynamics in these historically novel species assemblages.

Oak, chestnut and fire: climatic and cultural controls of long‐term forest dynamics in New England, USA - David R. Foster; Susan Clayden; David A. Orwig; Brian Hall; Sylvia Barry (Journal of Biogeography, 2002)
Aim Despite decades of study we have limited insights into the nature of the pre‐European landscape of the north‐eastern USA and the forces and changes that shaped modern forest patterns. Information on such long‐term forest dynamics would provide critical insights into the relationships among environmental change, land‐use history and biotic responses and is greatly needed for conservation planning. To address these issues we used modern, historical, and palaeoecological approaches to reconstruct the 3500‐year history of a New England upland region dominated by oak and (formerly) chestnut forests and to interpret the interactions among climate change, natural and human disturbance, and site factors in controlling vegetation patterns and dynamics at different spatial scales. Location The study focused on a broad upland ridge dominated by oak forests in the north‐central Massachusetts town of New Salem. Detailed palaeoecological analyses were undertaken of wetland (Chamberlain Swamp) and lake (Lily Pond) basins in order to reconstruct local to regional scale vegetation dynamics, which were interpreted within the context of regional vegetation data from central Massachusetts. Methods Palaeoecological methods were used to reconstruct the vegetation, fire and land‐use history of the local and subregional vegetation from the two basins and to place these in the context of regional information on vegetation and climate change based on other published data. Historical information including maps, archaeological and census data, and vegetation information were gathered for the landscape and areas surrounding the coring sites. Vegetation sampling in transects adjacent to the swamp coring area included tree cores for dendrochronological reconstructions. Results Stand, landscape and regional forest dynamics were most strongly driven by climate, notably an apparent cooling and increase in moisture availability c. 1500 yr bp , and European land‐use activities commencing 260 yr bp . However, the abundance of oak and chestnut (fire‐tolerant, sprouting species) and the distribution of hemlock (fire‐intolerant) at a stand to landscape scale were also influenced by fire, which, in turn, varied with climate and human activity. Despite, or perhaps as a consequence of ongoing disturbance by fire and presumably windstorms in this hurricane‐prone region, the pre‐European period was marked by two 1000+ year periods of remarkably stable forest composition, separated by an abrupt compositional shift. In contrast, over the past 260 years the vegetation has changed rather continuously in response to human activity, producing stand, landscape and regional patterns that are novel as well as recent in origin. The results indicate that chestnut was a major component of some pre‐European landscapes in New England, in part because of occasional fire, and that cultural and physical factors have interacted over millennia to control vegetation patterns and dynamics. Our analyses also suggest that the composition of low diversity forests can be remarkably stable over millennia. The range of ecological, cultural and management insights afforded by this study underscores the fundamental utility of very long‐term research in science and policy development.

The illusion of preservation: a global environmental argument for the local production of natural resources - Mary M. Berlik; David B. Kittredge; David R. Foster (Journal of Biogeography, 2002)
Aim The United States (US) and other affluent countries consume vast quantities of global natural resources, but contribute proportionately less to the extraction of many raw materials. This imbalance is due, in part, to domestic policies intended to protect the environment. Ironically, developed nations are often better equipped to extract resources in an environmentally prudent manner than the major suppliers. Thus, although citizens of affluent countries may imagine that preservationist domestic policies are conserving resources and protecting nature, heavy consumption rates necessitate resource extraction elsewhere and oftentimes under weak environmental oversight. A major consequence of this ‘illusion of natural resource preservation’ is greater global environmental degradation than would arise if consumption were reduced and a large portion of production was shared by affluent countries. This paper considers some implications of the consumption, management and conservation of forests and wood at a local and global scale. Location We focus on Massachusetts, the eighth most forested state in the USA (by area), the third most densely populated, and an affluent region with consumption rates that are among the highest in the country. Methods Estimates of wood production and consumption are generated, and comparisons are made with other commonly used materials (e.g. steel, concrete, aluminium). Results A comparison of the feasibility and environmental impact of various strategies for dealing with rising wood demand suggests that the US should strive to: (1) reduce per capita consumption of wood and its substitutes, (2) recycle forest products more effectively, (3) protect extensive areas of intensively managed and unmanaged forests and (4) promote sound forest management where the environmental consequences are mild. Forestry and the sustainable generation of wood in Massachusetts would allow preservation of primary forests elsewhere in the world. Main conclusions When aggressive reductions in wood consumption and effective recycling are combined with judiciously increased harvest levels, 50% of the Massachusetts's wood consumption could be met at sustainable rates, even while preserving large undisturbed blocks of forest.

Grasslands, heathlands and shrublands in coastal New England: historical interpretations and approaches to conservation - Glenn Motzkin; David R. Foster (Journal of Biogeography, 2002)
Aim This study evaluates the long‐term history of grassland, heathland and shrubland communities that are high priorities for conservation in the north‐eastern US and support numerous globally rare species. Such an historical perspective is necessary in order to develop appropriate conservation and management approaches for these communities. Location The study area encompasses the coastal region that extends from Cape Cod, MA to Long Island, NY, including the islands of Nantucket, Martha's Vineyard, and Block Island. Methods In order to determine whether open‐land habitats occurred in the study region prior to European arrival in the seventeenth century and to assess changes to these communities through the historical period, a wide range of palaeoecological, archaeological, ethno‐historical, biological and field data were reviewed. Information about the history of human impacts on these communities was used to interpret landscape change over time and to evaluate current and potential conservation and management approaches. Results The region was predominantly wooded prior to widespread Euro‐American land clearing beginning in the seventeenth century, with some areas of early successional habitats, primarily on exposed sites and near Native American settlements. Grasslands, heathlands and shrublands increased dramatically as a result of intensive and primarily agricultural disturbance through the historical period. The decline in recent decades of these communities results from extensive residential and commercial development, and from widespread abandonment of traditional agricultural practices, especially intensive grazing. Main conclusions Despite considerable uncertainty as to the pre‐European distribution and abundance of species characteristic of grasslands, heathlands and shrublands, historical disturbances have been sufficiently widespread and severe that it is unlikely that modern species assemblages closely resemble those that occurred prior to European arrival. Management aimed at perpetuating early successional species assemblages on sites other than exposed, coastal locations may require use of traditional land‐use practices or appropriate substitutes of comparable intensity.

Legacies of the agricultural past in the forested present: an assessment of historical land‐use effects on rich mesic forests - Jesse Bellemare; Glenn Motzkin; David R. Foster (Journal of Biogeography, 2002)
Aim and location The research investigated the long‐term effects of human disturbance, namely nineteenth century agricultural land‐use, on the modern species composition, structure and distribution of Rich Mesic Forests (RMF) in western Massachusetts, USA. RMF are a species‐rich north‐eastern variant of the Mixed Mesophytic Forest Type of eastern North America. Methods Land‐use history patterns were reconstructed for two towns ( c . 16,000 ha) from the onset of widespread European settlement and agricultural land‐use in the late eighteenth century until present. Vegetation and a range of environmental variables were sampled in sixty‐one 10 × 10 m plots in thirty‐four forest stands with varying histories of human disturbance. Vegetation data were ordinated (DCA) to identify patterns of variation and related environmental and historical factors. The distribution patterns of individual taxa in relation to historical land‐use and environmental factors were analysed using G ‐tests of independence and logistic regression. Associations between species secondary forest colonization ability and life history characteristics (e.g. diaspore dispersal mode, degree of vegetative spread) were assessed. Results Persistent compositional differences were documented between the vegetation of primary forests and post‐agricultural, secondary forests indicating that distribution patterns for many plant species still reflect the open, agricultural environment of the nineteenth century, despite the current predominance of forest cover in the study area. A major factor driving modern vegetation patterns in RMF is the ability and rate of colonization by forest herbs. In particular, species with seeds lacking morphological adaptations for dispersal (barochores) and those which produce seeds with elaiosomes to encourage ant dispersal (myrmecochores) are less frequent in secondary forests. Environmental differences between primary and secondary forests, although present, appear to be less important in influencing species distribution patterns. Main conclusions Widespread agricultural land‐use represents a novel disturbance in the naturally forested ecosystems of eastern North America with long‐term impacts on plant community composition and structure. Many secondary forest sites that are environmentally suitable for RMF vegetation do not support the suite of plant species typical of this community type, apparently because of the dispersal limitations of certain forest herbs. These poorly dispersed herb taxa are well adapted for growth in stable forest ecosystems characterized by local, small‐scale disturbance (e.g. gap‐phase dynamics), yet are maladapted for rapid population recovery and recolonization following severe disturbance (e.g. agricultural land‐use).

Cultural, environmental and historical controls of vegetation patterns and the modern conservation setting on the island of Martha's Vineyard, USA - David R. Foster; Brian Hall; Sylvia Barry; Susan Clayden; Tim Parshall (Journal of Biogeography, 2002)
Aim Long‐term studies of landscape dynamics in relationship to changes in cultural, environmental and disturbance factors have great potential for increasing the understanding of modern ecological conditions and improving the development of conservation plans that incorporate historically important processes. In this study we compiled archaeological, historical, palaeoecological and ecological information on Martha's Vineyard to investigate temporal and spatial variation in landscape pattern and process. Although 2 , this island off the Massachusetts coast embraces remarkable geographical variation and harbours uncommon plant and animal assemblages that make it a national priority for conservation. Location The study embraces the entire island of Martha's Vineyard, which lies c. 8 km south of Cape Cod and the mainland of Massachusetts. The triangular‐shaped island contains three major geomorphological regions: moraine forms a series of irregular and subparallel ridges and hills 40 to over 80 m in elevation that terminate at the western end of the island in high cliffs at Gay Head and Squibnocket; sandy glacial outwash overlying moraine spreads down the northeastern end of the island forming a region of low undulating hills and shallow depressions 15–30 m in elevation, and an extensive outwash plain stretches across the central and eastern part of the island and slopes gently from 30‐m elevation in the north to 100 m of Quaternary and coastal plain sediments. Methods Long‐term records of vegetation, fire, natural disturbance and human activity were compiled over the past 2000 years and across the physiographic variation on the island. Palaeoecological interpretations of vegetation, fire, climate and land‐use history are based on a series of eleven stratigraphies from ponds, lakes and wetlands; archaeological data were compiled from recent surveys; historical data were assembled from census and town records, fire records, aerial photographs and cartographic series; and ecological information was derived from forestry and conservation surveys and field sampling of vegetation, soils and site characteristics. Extensive use was made of geographical information systems and multivariate statistical analyses. Results Spatial patterns in vegetation over the past 2000 years have varied strongly with soils and physiography, which are also associated with major differences in fire and land‐use history. Mesic hardwood forests that seldom burned occupy the western moraine, open oak‐pine and hardwood forests occur on the frequently burned and dissected outwash plain along the south coast, and pine‐oak forests cover the central outwash plain, which extends across much of the island and displays among the highest charcoal values in New England. Although a relatively large Native American population may have been an important source of fire ignitions there is no palynological or archaeological evidence that this culture cleared substantial areas or directly altered the extent of forest cover. Shifts in forest composition and fire were associated with regional climate change during the pre‐European period, whereas pronounced changes in forest cover and the development of extensive open‐land areas of grassland, shrubland and heathland were driven by European land use. The contrasting characteristics, land‐use histories and ownerships of different regions of the island yield contrasting conservation priorities and management directions. The mesic morainal forests have changed modestly in composition during the historical period and can effectively support a distinct woodland flora if adequately protected. The large outwash plain is broken by non‐native plantations but could yield an effective landscape mosaic of oak and pine forests interrupted by extensive scrub oak barrens that could be maintained through prescribed fire or cutting. In contrast, the south shore grasslands and shrublands are the product of intensive agricultural land use. These habitats and their unusual suite of plants and animals require traditional land‐use practices, or their substitutes, in order to reverse the ongoing increase in woody species and to maintain these cultural landscapes. Main Conclusion The biotic, edaphic, disturbance and historical diversity across this relatively small landscape is remarkable and yet poses many challenges to interpretation and conservation. The modern landscape can only be understood through knowledge of its long‐term past and can be best managed in the context of the natural and cultural factors that have shaped it through time.

Insights from historical geography to ecology and conservation: lessons from the New England landscape - David R. Foster (Journal of Biogeography, 2002)

Conservation issues and approaches for dynamic cultural landscapes - David R. Foster (Journal of Biogeography, 2002)

Thoreau's country: a historical–ecological perspective on conservation in the New England landscape - David R. Foster (Journal of Biogeography, 2002)
Our wood‐lots, of course, have a history, and we may often recover it for a hundred years back, though we do not...Yet if we attended more to the history of our lots we should manage them more wisely. H.D. Thoreau. 16 October 1860. Henry Thoreau, the great New England writer, thinker and naturalist, devoted his ‘career’ to observing, describing and interpreting (in some 2 million words in more than three dozen journal volumes) the natural and cultural characteristics of his nineteenth century landscape. Through these writings we not only learn a great deal about our land and its ancestry but we receive an impassioned, although balanced reverence for both the wild and cultural sides of nature. Thoreau also presents a means of interpreting landscapes based on keen observation, a strong awareness of natural history, and a recognition that insights to modern nature often lie in its past [Foster, D.R. (1999) Thoreau's country. Journey through a transformed landscape . Harvard University Press, Cambridge]. This paper argues that we take Thoreau's words and approach to conservation to heart and admonishes that we appreciate the historical processes driving long‐term ecological changes as we attempt to conserve and restore the vegetation, wildlife and landscape of regions including New England. Over the past four centuries much of the eastern USA has been transformed by human activity as the heavily forested area was settled, cut, cleared and farmed through the mid‐nineteenth century and then largely abandoned in haphazard fashion from active use and allowed to reforest naturally [Cronon, W. (1983) Changes in the land Indians, colonists and the ecology of New England . Hill and Wang, New York; Whitney, G.G. (1994) From coastal wilderness to fruited plain . Cambridge University Press, Cambridge; Foster, D.R. & O'Keefe, J.F. (2000) New England forests through time: insights from the Harvard forest dioramas. Harvard Forest and Harvard University Press, Petersham and Cambridge; Hall, B. et al . (2002) Journal of Biogeography , 29 , 1319–1335]. Rather remarkably, the present landscape of New England supports many more natural attributes and processes than at any time since before the American Revolution. As a consequence of its history the region's considerable variation in vegetation, wildlife and appearance is largely explained by the history of human use [Bellemare, J. et al . (2002) Journal of Biogeography , 29 , 1401–1420; Gerhardt, F. & Foster, D.R. (2002) Journal of Biogeography , 29 , 1421–1437; Hall, B. et al . (2002) Journal of Biogeography , 29 , 1319–1335; Eberhardt, R. et al . (2003) Ecological Applications (in press)]. Thus, although the region supports a diverse range of species, plant and animal assemblages, and landscapes, successful conservation strategies need to be based on a broad‐scale approach that appreciates regional variation in natural and cultural history as well as current conditions [Foster, D.R. & Motzkin, G. (1998) Northeastern Naturalist , 5 , 111; Motzkin, G. & Foster, D.R. (2002) Journal of Biogeography , 29 , 1569–1589]. This approach must also work effectively with the general lack of regional planning and regulation and the predominant role of private ownership and control in New England [Berlik, M.M. et al . (2002) Journal of Biogeography , 29 , 1557–1568]. When a geographical–historical perspective is adopted for this region, three major, and in many ways quite dissimilar, directions for conservation emerge that are consistent with the region's history and environmental variation, are being actively pursued by conservation organizations and agencies, and might be effectively coordinated on a broad scale today. These directions, as articulated by diverse organizations include: (1) wilderness preservation and the restoration and the conservation of wide‐ranging species and broad‐scale ecological processes; (2) maintenance of cultural, predominantly agriculturally derived, landscapes; and (3) increased, environmentally sound harvesting and utilization of local forest resources. Individually, when applied in appropriate landscape contexts, each of these approaches can exert positive benefits on biodiversity, environmental processes and quality of life. When applied collectively in a coordinated geographical fashion that acknowledges and accommodates regional variation resulting from physical, biological, cultural and historical factors, these three directions in land management may provide a broad template for proactive conservation that generates local to global benefits. This paper examines each of these three conservation directions in relation to the region's history and current ecological condition, attempts to articulate the environmental rationale that supports these activities, and then presents an initial approach at positioning each across this varied region.

Vegetation and disturbance history of a rare dwarf pitch pine community in western New England, USA - Glenn Motzkin; David A. Orwig; David R. Foster (Journal of Biogeography, 2002)
Aim This study documents the vegetation history and age‐structure of a rare, ridgetop dwarf pine–oak community and compares the dynamics of this unusual vegetation with similar dwarf pine communities found elsewhere in the north‐eastern United States (US). Location The study area is located on the summit of Mt Everett in the Taconic Mountains of south‐western Berkshire County, Massachusetts, USA (42°06′N 73°26′W). Methods Vegetation composition, tree age‐structure, physical site characteristics, and evidence of fire and other disturbances were determined for twelve 15 × 15 m plots in dwarf pine–oak vegetation and two plots in oak forests on the summit. Age‐structure analyses, tree‐ring patterns, and historical records of human and natural disturbance were used to investigate the long‐term history and dynamics of the summit vegetation. Results The summit of Mt Everett has been dominated by dwarf pines (1–3 m tall) and ericaceous shrubs similar to the modern vegetation throughout the historical period; there is no evidence that tall‐stature forests occurred on the site at any point in the past few centuries. The summit supports uneven‐aged stands; pitch pine ( Pinus rigida ) recruitment began in the 1830s and occurred in every decade since the 1860s. Average pitch pine age is seventy‐eight with a range of 12–170 years. Red oak ( Quercus rubra ) and red maple ( Acer rubrum ) increased in importance in the twentieth century, with most stems establishing from 1940 to 1980. Pitch pine radial growth rates averaged −1 while red oak and red maple averaged 1.0 and 0.8 mm year −1 , respectively. In some areas, hardwoods have overtopped pitch pines, apparently resulting in pitch pine mortality. Whereas most dwarf pitch pine communities occur on sites that burn frequently and have a high degree of cone serotiny, we found no evidence of recent fires or cone serotiny. Small amounts of macroscopic charcoal that we documented may have resulted from fires in the pre‐European or early historical periods. Conclusions Harsh edaphic conditions and chronic low‐level disturbances on the summit, including frequent winter storms, have apparently contributed to the establishment, long‐term persistence, and slow radial growth of dwarf pitch pines on Mt Everett. The ability of dwarf pines to persist on a site in the absence of frequent fire is highly unusual among North‐eastern barrens and has not been well‐incorporated into previous conceptual ecological models of these communities. Our results suggest that even among North‐eastern barrens, the summit of Mt Everett is characterized by highly unusual vegetation and dynamics. The site has long been recognized as regionally significant and should be afforded the strictest conservation protection. With no evident history of human disturbance or recent fire, there is no apparent need for immediate active management of the site.

A geochronological framework for orogenic gold mineralisation in central Victoria, Australia - Frank P. Bierlein; Dennis C. Arne; David A. Foster; Peter Reynolds (Mineralium Deposita, 2001)

Ultrasound for the Visualization and Quantification of Tumor Microcirculation - F. Stuart Foster; Peter N. Burns; David H. Simpson; Stephanie R. Wilson; Donald A. Christopher; David E. Goertz (Cancer and Metastasis Reviews, 2000)

Dynamic and static views of succession: Testing the descriptive power of the chronosequence approach - Bryan L. Foster; David Tilman (Plant Ecology, 2000)

From bobolinks to bears: interjecting geographical history into ecological studies, environmental interpretation, and conservation planning - David R. Foster (Journal of Biogeography, 2000)
In these days of supercomputer‐based global climate models, large ecosystem experiments including Biosphere II, and aircraft‐borne sensors of ozone holes it is often overlooked that many fundamental insights into ecological processes and major environmental issues come not through reductionist or high‐tech studies of modern conditions but from thoughtful consideration of nature’s history. In fact, it is foolhardy to make any ecological interpretation of modern landscapes or environments or to formulate policy in conservation or natural resource management without an historical context that extends back decades, at least, but preferably centuries or millennia. Oftentimes, the ecological and conservation communities, in their search for more detail on the present and simulation of the future, appear to have forgotten the value of a deep historical perspective in research and application. However, the willingness of the geographical sciences to embrace broad temporal and spatial perspectives and to consider cultural as well as natural processes is worth emulating as we address environmental subjects in the new millennium.

Landscape Patterns and Legacies Resulting from Large, Infrequent Forest Disturbances - David R. Foster; Dennis H. Knight; Jerry F. Franklin (Ecosystems, 1998)

Soil carbon and nitrogen in a pine-oak sand plain in central Massachusetts: Role of vegetation and land-use history - Jana E. Compton; Richard D. Boone; Glenn Motzkin; David R. Foster (Oecologia, 1998)

Land-Use History as Long-Term Broad-Scale Disturbance: Regional Forest Dynamics in Central New England - David R. Foster; Glenn Motzkin; Benjamin Slater (Ecosystems, 1998)

Impact of Human Activity on Regional Forest Composition and Dynamics in Central New England - Janice L. Fuller; David R. Foster; Jason S. McLachlan; Natalie Drake (Ecosystems, 1998)

Accumulation and transport of nickel in relation to organic acids in ryegrass and maize grown with different nickel levels - Xiao E Yang; Virupaex C Baligar; Joyce C Foster; David C Martens (Plant and Soil, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Scale-up of Adhesive Transdermal Drug Delivery Systems - Glenn A. Van Buskirk; Mario A. González; Vinod P. Shah; Scott Barnhardt; Colin Barrett; Stephen Berge; Gary Cleary; Keith Chan; Gordon Flynn; Thomas Foster; Robert Gale; Raymond Garrison; et al. (Pharmaceutical Research, 1997)

History and Importance of Land Use and Protection in the North Quabbin Region of Massachusetts (USA) - Alisa D. Golodetz; David R. Foster (Conservation Biology, 1997)
Evaluating the consequences and future of land protection requires broad temporal and spatial perspectives of ecological and cultural factors. We assessed the development of a system of protected areas comprising 37% of central Massachusetts in terms of changing rates and means of land protection. We compared protected areas to the surrounding matrix in terms of physical, biological, and historical features and used these results to raise issues concerning future planning. The rate, purpose, and means of land protection in the North Quabbin Region (168,312 ha) have been dynamic as a result of changes in cultural values and transformation of the landscape from predominantly agriculture to forest. Protected lands are managed by 25 federal and state agencies, private groups, and municipal departments and commissions and are physically and biologically typical of the regional landscape which results from (1) participation of diverse organizations with varied agendas; (2) predominance of large government acquisitions driven by landscape‐scale criteria; and (3) absence of coordination among groups. The large area, relative homogeneity and largely undeveloped status of the North Quabbin Region suggest conservation goals distinct from those in the fragmented and extensively developed neighboring areas of the Connecticut River Valley and Cape Cod and Islands Region. Large tracts of forests, wetlands, and lakes in the North Quabbin Region provide (1) habitat for species requiring extensive, intact areas; (2) the opportunity to maintain broad‐scale ecological processes; (3) connections to regional conservation areas; and (4) recreation. To realize the area’s potential, a comprehensive plan must be based on a broad‐scale perspective and historical understanding of the landscape.

Viewpoint-invariant Weber fractions and standard contour-curvature discrimination - David H. Foster; Johan Wagemans (Biological Cybernetics, 1993)

Erratum - David H. Foster (Biological Cybernetics, 1986)

Estimating the variance of a critical stimulus level from sensory performance data - David H. Foster (Biological Cybernetics, 1986)

Internal representations and operations in the visual comparison of transformed patterns: Effects of pattern point-inversion, positional symmetry, and separation - David H. Foster; Jeremy I. Kahn (Biological Cybernetics, 1985)

Characterization of discrete and continuous modes of visual pattern discrimination - Mario Ferraro; David H. Foster (Biological Cybernetics, 1984)

A description of discrete internal representation schemes for visual pattern discrimination - David H. Foster (Biological Cybernetics, 1980)

A spatial perturbation technique for the investigation of discrete internal representations of visual patterns - David H. Foster (Biological Cybernetics, 1980)

Transformation and relational-structure schemes for visual pattern recognition - David H. Foster; Robert J. Mason (Biological Cybernetics, 1979)

Visual apparent motion and some preferred paths in the rotation group SO(3) - David H. Foster (Biological Cybernetics, 1975)

An approach to the analysis of the underlying structure of visual space using a generalized notion of visual pattern recognition - David H. Foster (Biological Cybernetics, 1975)